Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Microbiome baseline for an Arctic sentinel: spatial patterning of nasal and anal microbiomes in ringed seals - Carlos A. Domínguez-Sánchez; Olwyn C. Friesen; Brent G. Young; Tera L. Edkins; Ellen V. Lea; Magali Houde; Stephen D. Petersen; David J. Yurkowski; Holly E. L. Gamblin; Steve H. Ferguson (Frontiers in Marine Science, 2026)
Introduction Ringed seals ( Pusa hispida ) are sentinel species of Arctic change, yet baseline microbiome data across their circumpolar range remain limited. Methods We profiled nasal and anal microbiomes from 90 free-ranging ringed seals across eight Arctic and sub-Arctic locations in Canada using 16S rRNA gene amplicon sequencing. Results Body site was the primary determinant of microbiome structure, with nasal and anal assemblages forming distinct communities that could be classified with 94.8% accuracy, consistent with strong niche partitioning. Nasal microbiomes exhibited a conserved core dominated by the genera Corynebacterium, Psychrobacter , and Suttonella across all sampling locations, supporting a stable respiratory baseline consistent with host-mediated filtering. In contrast, anal microbiomes showed higher richness, greater inter-individual variability, and a latitudinal gradient in diversity: Shannon index, Pielou’s evenness, and Simpson index all declined with increasing latitude (all p < 0.05), suggesting that ecological constraints at higher latitudes promote dominance by a narrower set of taxa without reducing overall richness. Despite overall compositional differences among locations, geographic distance was a poor predictor of microbiome dissimilarity in both body sites. Instead, continuous spatial gradients of latitude and longitude were associated with microbiome composition in both body sites: in nasal microbiomes, genus Corynebacterium increased while Ornithobacterium and Suttonella decreased at higher latitudes, whereas in anal microbiomes, Psychrobacter and Peptoclostridium increased northward while Fusobacterium and Bacteroides declined, patterns not previously reported in Arctic pinnipeds. Conclusion Together, these findings establish the first integrated nasal and anal microbiome baseline for ringed seals, demonstrate that the two body sites provide complementary ecological signals, and establish a reference framework for future microbiome-based health monitoring in a rapidly changing Arctic.

A Numerical Study of Eastern Oyster (Crassostrea virginica) Larval Growth and Dispersal in Barataria Estuary, Louisiana, USA - Zhengchen Zang; Z. George Xue; Shaye E. Sable; Megan K. La Peyre; Kenneth A. Rose; Timothy A. Stephens; Brady Carter; David C. Lindquist; Yanda Ou; Ziyan Lei (Estuaries and Coasts, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Isotopic constraints on volcano-tectonically controlled assimilation at Campi Flegrei, Italy - Fay M. Amstutz; Michael J. Stock; Victoria C. Smith; Roberto Isaia; David van Acken; Stefano Vitale; Jacopo Natale; J. Stephen Daly; Adrian Boyce (Chemical Geology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Development of new global lake brGDGT-temperature calibrations: advances, applications, challenges, and recommendations - Emma J. Pearson; Steve Juggins; Harry Allbrook; Louise C. Foster; Dominic A. Hodgson; B. David A. Naafs; Tony Phillips; Stephen J. Roberts (Quaternary Science Reviews, 2025)

Census collection of two fossil plant localities in Jameson Land, East Greenland supports regional ecological turnover and diversity loss at the end-Triassic mass extinction - Antonietta B. Knetge; Catarina Barbosa; William J. Matthaeus; Richard S. Barclay; Ian J. Glasspool; Bernard Gomez; Stephen P. Hesselbo; Mihai E. Popa; Micha Ruhl; David Sunderlin; Finn Surlyk; Jennifer C. McElwain (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Analysis of source regions and transport pathways of sub-micron aerosol components in Europe - Michelle Y. Schneider; Jianhui Jiang; Ying Chen; Wenche Aas; Samira Atabakhsh; Minna Aurela; Claudio Belis; Aikaterini Bougiatioti; Michael Bressi; Francesco Canonaco; Benjamin Chazeau; Hasna Chebaicheb; et al. (Environmental Pollution, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Correction to: Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)

Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)
Rationale Psilocybin is a potentially paradigm-shifting depression intervention. We conducted a systematic review and meta-analysis of psilocybin-for-depression randomized controlled trials (RCTs). Objectives Systematically assess harm reporting, risk of bias, action mechanism specification, and incremental therapeutic effect sizes in the psilocybin-for-depression RCT literature. Methods Assessed databases included PsycINFO, CINAHL, Embase, Medline, Web of Science, and Scopus. Search terms “Psilocybin” or “Psychedelic” were paired with “Depression”, and "Randomized Controlled Trial" or “RCT”. Results We identified k = 9 RCTs ( k = 10 subgroups) involving n = 602 participants (56% psilocybin). Five studies had low/very low harm quality reporting, opposed to two with high. Most studies demonstrated a high risk of bias. Therapeutic mechanisms of action (MoAs) were discussed in varying detail but rarely assessed in original publications. Psilocybin was moderately superior to controls at reducing depression ( g = 0.62; 95% CI = 0.27, 0.98). Effects were heterogenous (τ = .47). Smaller studies evidenced stronger effects that favored psilocybin (Egger’s b 0 = 3.63, p = .014). Almost all studies documented financial conflicts of interests. Conclusion Psilocybin demonstrates significant depression reduction relative to controls. However, researchers, clinicians, and stakeholders should consider several contextual factors. Effects were moderate and attenuated in larger and better-controlled studies. Harms reporting and risk of bias was high, though partly driven by unique challenges of psilocybin research. MoAs were variably specified but rarely assessed; suggesting it is unclear how depression is reduced. We advise researchers conduct RCTs with active control conditions, larger samples, and include MoA assessments. Independent RCTs from researchers without financial conflicts of interest are needed.

Population genomics of rainforest mountain frogs (Anura: Limnodynastidae: Philoria) severely impacted by the Australian megafires - Shengyao Lin; David Newell; Nicola J. Mitchell; Stephen C. Donnellan; Michael Mahony; Liam J. Bolitho; Renee A. Catullo (Conservation Genetics, 2025)
The 2019/20 Australian megafires impacted numerous species, including six of the seven montane frog species from the genus Philoria , which are restricted to the top of mountain habitats across eastern Australian Gondwana Rainforest. Using single nucleotide polymorphisms, we examined the population structure and genetic diversity of the six Philoria species to inform conservation management and assess their capacity for post-fire recovery. Narrow-range species were confirmed as a single population for management purposes, while P. kundagungan , P. loveridgei , and P. sphagnicolus exhibit marked genetic differentiation between populations, indicating strong allopatric differentiation among populations isolated on separate mountaintops, suggesting limited natural dispersal ability. We further identify high-value genetic populations in these structured species. Populations that were heavily impacted by the fires, such as P. pughi and P. knowlesi , may face longer-term threats due to potential declines in adaptive capacity. We recommend prioritising in situ management, genetic rescue, and translocation efforts to bolster resilience in isolated populations. Updated conservation planning and targeted fire buffer management are crucial for the survival of these ancient, regionally endemic frogs in a rapidly changing climate.

Nutrients on the move: Investigating large scale fatty acid exports from European ponds via emerging insects - Lena Fehlinger; Fernando Chaguaceda; Pietro Tirozzi; Marina Tomás‐Martín; Ellinor Jakobsson; Teofana Chonova; Benjamin Misteli; Alberto Scotti; Jorge F. Henriques; Juan Rubio‐Ríos; Daniel Morant; Pierre Marle; et al. (Limnology and Oceanography, 2025)
Permanent ponds are key landscape units that supply various ecosystem services. Notably, the export of aquatic subsidies to land via emerging insects may significantly influence terrestrial food webs. Polyunsaturated fatty acids (PUFA), which enhance consumer fitness, are among the essential exported components. The patterns and drivers of dietary exports from ponds via insects remain poorly known, particularly at continental scales. We analyzed the exports of biomass, lipid, and fatty acid contents from emerging insects, sampled in 36 ponds across 11 European countries, from 36°N to 59°N and from 26°W to 19°E, over four seasons. We found that biomass and fatty acid exports decreased with increasing latitude and were higher in spring and summer. Seasonal effects also increased with higher latitudes. Temperature was the most important predictor of insect biomass, explaining 27.6% of the total variation and showing an unimodal response. Thus, increasing temperature may promote exports in colder regions and seasons but may negatively influence biomass exports in already warm regions. The exports of total lipids, PUFA, and eicosapentaenoic acid were correlated to exported biomass, while those of docosahexaenoic acid were linked to the emergence of Chaoboridae. Our findings indicated that PUFA contents were affected by taxonomic insect community composition and pond trophic state (indicated by chlorophyll a ). Two of the correlates identified here (temperature and trophic state) are influenced by anthropogenic activity via climate and land use change, respectively. Thus, human activity impacts the food webs in and around ponds by influencing the quantity and quality of nutritional exports.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Habitat Conversion by Native Spartina Highlights the Importance of Wetland Restoration Design Relative to Site-Specific Vertical Range of Vegetation - Rachel S. Smith; Emily Blair; Andres Deza; Justin C. Hoesterey; David Huang; Russell Johnston; Henry M. Page; Stephen C. Schroeter; Morgan Tusa; Denise Weisman; Kathryn M. Beheshti (Estuaries and Coasts, 2025)
Native vegetation is planted in wetland restoration projects to supplement natural recruitment and achieve a habitat mix that supports ecological functioning. The native cordgrass Spartina foliosa —an ecosystem engineer with a wide elevation range—is frequently planted in wetland restorations in Southern California to jumpstart low marsh development. Although plantings can increase vegetation cover, planted S. foliosa can also convert areas designed as tidal creeks or mudflat to salt marsh, hindering progress towards restoration objectives. At the restored San Dieguito Wetlands (SDW) in Southern California , S. foliosa was planted during (2008–2009) and after wetland construction (2011–2018). In 2023, S. foliosa occupied 10.8 ha at SDW, but had converted 42% of built tidal creek and mudflat habitat to salt marsh. Genetic testing ruled out potential hybridization with non-native Spartina . Tidal creek elevations were higher at SDW than at other California wetlands, overlapping with the design elevation of low marsh for the site. Spartina foliosa extended to lower elevations at SDW than other California wetlands, overlapping with the design elevation of mudflat for the site. Thus, habitat conversion at SDW was likely due to insufficient excavation of built tidal creeks and the lower than expected elevation range of S. foliosa at the site. Much of the existing tidal creek and mudflat habitat at SDW is likely susceptible to habitat conversion to salt marsh. Our results emphasize the need to consider the design elevation of restored habitats relative to site-specific elevation ranges of target wetland species.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

The Mechanisms Through Which Fire Drives Population Change in Terrestrial Biota - Ella Plumanns‐Pouton; Julianna L. Santos; Cristina Aponte; Lluís Brotons; Luke T. Kelly; Stephen C. Mason; Kirsten Parris; Lauren Ponisio; David A. Keith (Global Change Biology, 2025)
Global fire regime change is threatening terrestrial biodiversity. Understanding how these changes affect biota is essential to protect biodiversity now and into the future. A targeted examination of the mechanisms through which fire influences populations will help achieve this by enabling comparisons and connections across taxa. Here, we develop a cross‐taxa framework that identifies mechanisms through which fire regimes influence terrestrial species populations over different time scales, and traits on which those mechanisms depend. We focus on amphibians, birds, fungi, insects, mammals, plants, and reptiles. First, we identify key mechanisms through which fire regimes influence species populations across different taxonomic groups. Second, we link these mechanisms to functional traits that influence the relevance to different species. Third, we identify traits that shape the vulnerability—or conversely, resilience—of species populations to frequent, high‐intensity, and large wildfires that are emerging as a threat in many parts of the world. Finally, we highlight how this integrative framework can be useful for understanding and identifying fire‐related threats common to different taxa across the globe and for guiding future research on fire‐related population change.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

AviList: a unified global bird checklist - Frank E. Rheindt; Paul F. Donald; David B. Donsker; Jeffrey A. Gerbracht; Marshall J. Iliff; Denis Lepage; Janette A. Norman; Pamela C. Rasmussen; Richard Schodde; Thomas S. Schulenberg; Juan I. Areta; Frederik P. Brammer; et al. (Biodiversity and Conservation, 2025)

A unique Equisetum enzyme, hetero-trans-β-glucanase (HTG), enhances industrially and environmentally important cellulose-rich materials - Lenka Franková; Eric Whale; David Hepworth; Stephen C. Fry (Environmental Research, 2025)

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Genome-wide association analysis identifies seven loci conferring resistance to multiple wheat foliar diseases, including brown and yellow rust resistance originating from Aegilops ventricosa - Keith A. Gardner; Bethany Love; Pauline Bansept-Basler; Tobias Barber; Simon Berry; Nick Bird; Finn Borum; Lesley Boyd; James K. M. Brown; Ruth Bryant; Paul Fenwick; David Feuerhelm; et al. (Theoretical and Applied Genetics, 2025)
We assembled a European bread wheat ( Triticum aestivum L.) association mapping panel ( n = 480) genotyped using a 90,000 feature single nucleotide polymorphism array, with the aim of identifying genetic loci controlling resistance to four fungal diseases: yellow (stripe) rust (YR), brown (leaf) rust (BR), Septoria tritici blotch (ST) and powdery mildew (PM). Simulations showed our panel to have good power to detect genetic loci, with > 50% probability of identifying loci controlling as little as 5% of the variance when heritability was 0.6 or more. Using disease infection data collected across 31 trials undertaken in five European countries, genome-wide association studies (GWAS) identified 34 replicated genetic loci (20 for YR, 12 for BR, two for PM, 0 for ST), with seven loci associated with resistance to two or more diseases. Construction and analysis of eight bi-parental populations enabled two selected genetic loci, yellow rust resistance locus YR_2A010 (chromosome 2A) and YR_6A610 (6A), to be independently cross-validated, along with the development of genetic markers to track resistance alleles at these loci. Notably, the chromosome 2A yellow and brown rust resistance locus corresponds to the 2N v S introgression from the wild wheat species, Aegilops ventricosa . We found evidence of strong selection for 2N v S over recent breeding history, being present in 48% of the most recent cultivars in our panel. Collectively, we define the genetic architectures controlling resistance to major fungal diseases of wheat under European field environments, and provide resources to exploit these for the development of new wheat cultivars with improved disease resistance.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

When can we detect lianas from space? Toward a mechanistic understanding of liana‐infested forest optics - Marco D. Visser; Matteo Detto; Félicien Meunier; Jin Wu; Jane R. Foster; David C. Marvin; Peter M. van Bodegom; Boris Bongalov; Matheus Henrique Nunes; David Coomes; Hans Verbeeck; J. Antonio Guzmán Q; et al. (Ecology, 2025)
Lianas, woody vines acting as structural parasites of trees, have profound effects on the composition and structure of tropical forests, impacting tree growth, mortality, and forest succession. Remote sensing could offer a powerful tool for quantifying the scale of liana infestation, provided the availability of robust detection methods. We analyze the consistency and global geographic specificity of spectral signals—reflectance across wavelengths—from liana‐infested tree crowns and forest stands, examining the underlying mechanisms of these signals. We compiled a uniquely comprehensive database, including leaf reflectance spectra from 5424 leaves, fine‐scale airborne reflectance data from 999 liana‐infested canopies, and coarse‐scale satellite reflectance data covering 775 ha of liana‐infested forest stands. To unravel the mechanisms of the liana spectral signal, we applied mechanistic radiative transfer models across scales, establishing a synthesis of the relative importance of different mechanisms, which we corroborate with field data on liana leaf chemistry and canopy structure. We find a consistent liana spectral signal at canopy and stand scales across globally distributed sites. This signature mainly arises at the canopy level due to direct effects of more horizontal leaf angles, resulting in a larger projected leaf area, and indirect effects from increased light scattering in the near and short‐wave infrared regions, linked to lianas' less costly leaf construction compared with trees on average. The existence of a consistent global spectral signal for lianas suggests that large‐scale quantification of liana infestation is feasible. However, because the traits responsible for the liana canopy‐reflectance signal are not exclusive to lianas, accurate large‐scale detection requires rigorously validated remote sensing methods. Our models highlight challenges in automated detection, such as potential misidentification due to leaf phenology, tree life history, topography, and climate, especially where the scale of liana infestation is less than a single remote sensing pixel. The observed cross‐site patterns also prompt ecological questions about lianas' adaptive similarities in optical traits across environments, indicating possible convergent evolution due to shared constraints on leaf biochemical and structural traits.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Substrate Origin Controls Phosphorus Availability in Globally Distributed Long-Term Chronosequences - Tadeo Sáez-Sandino; Antonio Gallardo; Jorge Durán; David A. Wardle; Patrick E. Hayes; Stephen C. Hart; Laura García-Velázquez; Cecilia A. Pérez; Christina Siebe; Asmeret Asefaw Berhe; Manuel Delgado-Baquerizo (Ecosystems, 2025)
Phosphorus (P) is one of the most important elements for soil biology and biogeochemistry worldwide. Yet, despite decades of research, important uncertainties persist about the drivers and changes in soil P forms during long-term soil formation. Here, we analyzed topsoils from nine globally distributed retrogressive soil chronosequences aiming to evaluate the relative contribution of key environmental factors (that is, soil age, substrate origin, climate, soil attributes, and vegetation) in explaining the long-term dynamics of primary, occluded, non-occluded, organic, and total P across different terrestrial ecosystems. We found that, rather than soil age, substrate origin was the main driver controlling the fate of different P fractions across contrasting environmental conditions. Moreover, our findings suggest that temporal patterns governing the long-term dynamics of different P forms as soils develop are not consistent among soil chronosequences, which is a result of contrasting environmental conditions, especially substrate origin. We further showed that topsoil total P was the greatest at intermediate soil development stage across the globe. Lastly, our results showed that P fractions were highly correlated with multiple surrogates of ecosystem services, such as carbon sequestration, plant productivity, and biodiversity. Together, our work provides new insights into the natural history of P availability, and further highlights that substrate origin, rather than soil age, is essential to predict changes in P availability in response to physical perturbation and climate change.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Ecomorphology of Longnose Gar (Lepisosteus osseus): on the influence of size, sex, and river location - Jason C. Doll; Ian Fisher; Aaron Selby; Stephen J. Jacquemin; Daniel Sinopoli; Solomon R. David (Environmental Biology of Fishes, 2024)
Ecomorphology is essential to understanding the evolution and biogeography of species. However, morphological studies that focus on nongame or ‘rough’ fish groups such as Gar (Lepisosteidae), outside of a phylogenetic context, are comparatively rare. Herein, we investigate the effects of sex, size, and location in a river to assess the potential for sexual dimorphism, allometry, habitat, or some combination to drive observed morphologic variation. Our dataset includes 230 Longnose Gars ( Lepisosteus osseus ) made up of both males and females of a wide range of sizes collected from three different sites corresponding to the upper, middle, and lower Great Pee Dee River in South Carolina. Dorsal and lateral photographs were taken from each specimen and landmarked for 2D geometric morphometric analyses. Discriminant function analyses (DFA) were also conducted on a few linear trusses to compare the accuracy of sex-related shape aspects that emerged from morphometrics as a possible field-based tool to help fisheries managers understand their stock populations. Overall, location was a statistically significant predictor of shape, yet the differences were not biologically meaningful. Additionally, sex and size were strong predictors of shape, with the greatest differences seen in the largest individuals. DFA of field measurements found that the Snout Length-to-Total Length ratio accurately predicted sex 71% of the time, with females having longer snouts than males. Differences in ratio between sexes can allow tentative sex assignments without lethal gonadal inspection. This study presents the first standardized whole-body 2D geometric morphometrics protocol for Longnose Gar.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Orbiting Carbon Observatory-2 (OCO-2) and in situ CO2 data suggest a larger seasonal amplitude of the terrestrial carbon cycle compared to many dynamic global vegetation models - Ruixue Lei; Jeralyn Poe; Deborah Huntzinger; Junjie Liu; Stephen Stich; David F. Baker; Leyang Feng; Dylan C. Gaeta; Ziting Huang; Scot M. Miller (Remote Sensing of Environment, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Biologging reveals rapid movements of harbour seals between freshwater and marine habitats in the subarctic - Katie R.N. Florko; David J. Yurkowski; C-Jae C. Breiter; Steven H. Ferguson; Holly E.L. Gamblin; Adam Grottoli; Andrea Nace; Courtney R. Shuert; Stephen D. Petersen (Frontiers in Marine Science, 2024)
Biologging tools can provide invaluable information on the movement and behaviour of animals, facilitating the elucidation of ecological dynamics, especially for wide-ranging species, and supporting conservation and management efforts. Harbour seals ( Phoca vitulina ) exhibit extensive habitat plasticity in their vast range across the northern hemisphere, with likely recent increases in abundance at northern latitudes, yet details of their movement behaviour in subarctic areas remain largely unknown. We used satellite-telemetry data, including nearly 5,000 locations and over 12,000 dives, obtained from six harbour seals tagged in western Hudson Bay from 2021 to 2023, to address the knowledge gap on their movement behaviour between marine and freshwater habitats in subarctic regions. We document the behavioural patterns, transit speeds, and diverse aquatic system usage, including detailed records of a harbour seal track traversing over 170 km upriver on three separate trips along the Seal River, Canada. Notably, we observed a rapid downstream transit from the Seal River to Hudson Bay, covering 214 km within a single day. Additionally, we highlight the prevalence of short dive durations in the Seal and Churchill Rivers, in contrast to longer dive durations in Hudson Bay. These insights complement existing evidence of harbour seal occurrences and river use at northern latitudes, as well as enhance our understanding of harbour seal movement ecology within Hudson Bay which can be used to better inform conservation and management strategies between connected freshwater and marine environments in the Arctic.

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

A first look at CRISM hyperspectral mapping mosaicked data: Results from Mawrth Vallis - Michael S. Phillips; Scott L. Murchie; Frank P. Seelos; Katie M. Hancock; Christina Selby; Ryan T. Poffenbarger; David C. Stephens; Maia Kawamura (Icarus, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Integrated modeling of nature’s role in human well-being: A research agenda - Rebecca Chaplin-Kramer; Stephen Polasky; Rob Alkemade; Neil D. Burgess; William W.L. Cheung; Ingo Fetzer; Mike Harfoot; Thomas W. Hertel; Samantha L.L. Hill; Justin Andrew Johnson; Jan H. Janse; Patrick José v. Jeetze; et al. (Global Environmental Change, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Non-chlorine detergent formulations as an alternative for unpasteurised milk removal from stainless steel surfaces - Joels Wilson-Nieuwenhuis; Jim Taylour; Luciana C. Gomes; Stephen Lynch; David Whitehead; Kathryn A. Whitehead (Journal of Food Engineering, 2024)

Walking net $$\dot{V}$$O2 rises with advancing age in older women: where to go from here? - Stephen J. Carter; Harshvardhan Singh; Emily B. Long; Catia Martins; John P. McCarthy; C. Scott Bickel; David R. Bryan; Gary R. Hunter (European Journal of Applied Physiology, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

A circumpolar study unveils a positive non‐linear effect of temperature on arctic arthropod availability that may reduce the risk of warming‐induced trophic mismatch for breeding shorebirds - Aurélie Chagnon‐Lafortune; Éliane Duchesne; Pierre Legagneux; Laura McKinnon; Jeroen Reneerkens; Nicolas Casajus; Kenneth F. Abraham; Élise Bolduc; Glen S. Brown; Stephen C. Brown; H. River Gates; Olivier Gilg; et al. (Global Change Biology, 2024)
Seasonally abundant arthropods are a crucial food source for many migratory birds that breed in the Arctic. In cold environments, the growth and emergence of arthropods are particularly tied to temperature. Thus, the phenology of arthropods is anticipated to undergo a rapid change in response to a warming climate, potentially leading to a trophic mismatch between migratory insectivorous birds and their prey. Using data from 19 sites spanning a wide temperature gradient from the Subarctic to the High Arctic, we investigated the effects of temperature on the phenology and biomass of arthropods available to shorebirds during their short breeding season at high latitudes. We hypothesized that prolonged exposure to warmer summer temperatures would generate earlier peaks in arthropod biomass, as well as higher peak and seasonal biomass. Across the temperature gradient encompassed by our study sites (>10°C in average summer temperatures), we found a 3‐day shift in average peak date for every increment of 80 cumulative thawing degree‐days. Interestingly, we found a linear relationship between temperature and arthropod biomass only below temperature thresholds. Higher temperatures were associated with higher peak and seasonal biomass below 106 and 177 cumulative thawing degree‐days, respectively, between June 5 and July 15. Beyond these thresholds, no relationship was observed between temperature and arthropod biomass. Our results suggest that prolonged exposure to elevated temperatures can positively influence prey availability for some arctic birds. This positive effect could, in part, stem from changes in arthropod assemblages and may reduce the risk of trophic mismatch.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Why do avian responses to change in Arctic green‐up vary? - Eveling A. Tavera; David B. Lank; David C. Douglas; Brett K. Sandercock; Richard B. Lanctot; Niels M. Schmidt; Jeroen Reneerkens; David H. Ward; Joël Bêty; Eunbi Kwon; Nicolas Lecomte; Cheri Gratto‐Trevor; et al. (Global Change Biology, 2024)
Global climate change has altered the timing of seasonal events (i.e., phenology) for a diverse range of biota. Within and among species, however, the degree to which alterations in phenology match climate variability differ substantially. To better understand factors driving these differences, we evaluated variation in timing of nesting of eight Arctic‐breeding shorebird species at 18 sites over a 23‐year period. We used the Normalized Difference Vegetation Index as a proxy to determine the start of spring (SOS) growing season and quantified relationships between SOS and nest initiation dates as a measure of phenological responsiveness. Among species, we tested four life history traits (migration distance, seasonal timing of breeding, female body mass, expected female reproductive effort) as species‐level predictors of responsiveness. For one species (Semipalmated Sandpiper), we also evaluated whether responsiveness varied across sites. Although no species in our study completely tracked annual variation in SOS, phenological responses were strongest for Western Sandpipers, Pectoral Sandpipers, and Red Phalaropes. Migration distance was the strongest additional predictor of responsiveness, with longer‐distance migrant species generally tracking variation in SOS more closely than species that migrate shorter distances. Semipalmated Sandpipers are a widely distributed species, but adjustments in timing of nesting relative to variability in SOS did not vary across sites, suggesting that different breeding populations of this species were equally responsive to climate cues despite differing migration strategies. Our results unexpectedly show that long‐distance migrants are more sensitive to local environmental conditions, which may help them to adapt to ongoing changes in climate.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Applying microelectrodes to investigate aged ductile iron and copper coupon reactivity during free chlorine application - Jennifer E. Liggett; Beatriz C. Gonzalez; Darren A. Lytle; Jonathan G. Pressman; Dionysios D. Dionysiou; Woo Hyoung Lee; Stephen M. Harmon; David G. Wahman (Water Research, 2024)

Design of a randomized, placebo-controlled study evaluating efficacy and safety of a cancer preventative vaccine in dogs - Jenna H. Burton; Stephen Albert Johnston; David M. Vail; Jens C. Eickhoff; Kathryn F. Sykes; Justin R. Brown; Luhui Shen; Ana Gervassi; Rodney L. Page; Jennifer L. Willcox; Sami Al-Nadaf; Amanda L. Willis; et al. (Veterinary Immunology and Immunopathology, 2024)

Few havens for threatened Australian animal taxa that are highly susceptible to introduced and problematic native species - John C. Z. Woinarski; David G. Chapple; Stephen T. Garnett; Sarah M. Legge; Mark Lintermans; Ben C. Scheele (Biodiversity and Conservation, 2024)

Mouse phenome database: curated data repository with interactive multi-population and multi-trait analyses - Molly A. Bogue; Robyn L. Ball; David O. Walton; Matthew H. Dunn; Georgi Kolishovski; Alexander Berger; Anna Lamoureux; Stephen C. Grubb; Matthew Gerring; Matthew Kim; Hongping Liang; Jake Emerson; et al. (Mammalian Genome, 2023)
The Mouse Phenome Database continues to serve as a curated repository and analysis suite for measured attributes of members of diverse mouse populations. The repository includes annotation to community standard ontologies and guidelines, a database of allelic states for 657 mouse strains, a collection of protocols, and analysis tools for flexible, interactive, user directed analyses that increasingly integrates data across traits and populations. The database has grown from its initial focus on a standard set of inbred strains to include heterogeneous mouse populations such as the Diversity Outbred and mapping crosses and well as Collaborative Cross, Hybrid Mouse Diversity Panel, and recombinant inbred strains. Most recently the system has expanded to include data from the International Mouse Phenotyping Consortium. Collectively these data are accessible by API and provided with an interactive tool suite that enables users’ persistent selection, storage, and operation on collections of measures. The tool suite allows basic analyses, advanced functions with dynamic visualization including multi-population meta-analysis, multivariate outlier detection, trait pattern matching, correlation analyses and other functions. The data resources and analysis suite provide users a flexible environment in which to explore the basis of phenotypic variation in health and disease across the lifespan.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Antioxidants green tea extract and nordihydroguaiaretic acid confer species and strain-specific lifespan and health effects in Caenorhabditis nematodes - Stephen A. Banse; Christine A. Sedore; Erik Johnson; Anna L. Coleman-Hulbert; Brian Onken; David Hall; E. Grace Jackson; Phu Huynh; Anna C. Foulger; Suzhen Guo; Theo Garrett; Jian Xue; et al. (GeroScience, 2023)
The Caenorhabditis Intervention Testing Program (CITP) is an NIH-funded research consortium of investigators who conduct analyses at three independent sites to identify chemical interventions that reproducibly promote health and lifespan in a robust manner. The founding principle of the CITP is that compounds with positive effects across a genetically diverse panel of Caenorhabditis species and strains are likely engaging conserved biochemical pathways to exert their effects. As such, interventions that are broadly efficacious might be considered prominent compounds for translation for pre-clinical research and human clinical applications. Here, we report results generated using a recently streamlined pipeline approach for the evaluation of the effects of chemical compounds on lifespan and health. We studied five compounds previously shown to extend C. elegans lifespan or thought to promote mammalian health: 17α-estradiol, acarbose, green tea extract, nordihydroguaiaretic acid, and rapamycin. We found that green tea extract and nordihydroguaiaretic acid extend Caenorhabditis lifespan in a species-specific manner. Additionally, these two antioxidants conferred assay-specific effects in some studies—for example, decreasing survival for certain genetic backgrounds in manual survival assays in contrast with extended lifespan as assayed using automated C. elegans Lifespan Machines. We also observed that GTE and NDGA impact on older adult mobility capacity is dependent on genetic background, and that GTE reduces oxidative stress resistance in some Caenorhabditis strains. Overall, our analysis of the five compounds supports the general idea that genetic background and assay type can influence lifespan and health effects of compounds, and underscores that lifespan and health can be uncoupled by chemical interventions.

Estuarine-coastal connectivity and partial migration of southern flounder in the Gulf of Mexico - Christopher Steffen; Shane Stephens; Michael A. Dance; Daniel L. Lippi; Christine C. Jensen; R.J. David Wells; Jay R. Rooker (Estuarine, Coastal and Shelf Science, 2023)

Advancing chemical lability assessments of organic matter using a synthesis of FT-ICR MS data across diverse environments and experiments - Juliana D'Andrilli; Carlos M. Romero; Phoebe Zito; David C. Podgorski; Robert A. Payn; Stephen D. Sebestyen; Andrew R. Zimmerman; Fernando L. Rosario-Ortiz (Organic Geochemistry, 2023)

Strong breeding colony fidelity in northern gannets following high pathogenicity avian influenza virus (HPAIV) outbreak - David Grémillet; Aurore Ponchon; Pascal Provost; Amandine Gamble; Mouna Abed-Zahar; Alice Bernard; Nicolas Courbin; Grégoire Delavaud; Armel Deniau; Jérôme Fort; Keith C. Hamer; Ruth Jeavons; et al. (Biological Conservation, 2023)

Den site selection by eastern spotted skunks (Spilogale putorius) in the Blue Ridge Mountains, North Carolina - Anna C. Siegfried; Stephen N. Harris; Colleen Olfenbuttel; David S. Jachowski (Mammal Research, 2023)

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Jansen Smith; Marina C. Rillo; Ádám T. Kocsis; Maria Dornelas; David Fastovich; Huai‐Hsuan M. Huang; Lukas Jonkers; Wolfgang Kiessling; Qijian Li; Lee Hsiang Liow; Miranda Margulis‐Ohnuma; Stephen Meyers; et al. (Global Ecology and Biogeography, 2023)
Motivation We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present‐day to millions of years ago. Main Types of Variables Included BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm 2 to grid cells of ~100 km 2 . Time Period and Grain BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format SQLite, Comma‐separated values.

Editorial - Stephen C. Bowden; David W. Loring (Neuropsychology Review, 2023)

The spontaneous mouse mutant low set ears (Lse) is caused by tandem duplication of Fgf3 and Fgf4 - Alana Luzzio; Sarah Edie; Kristina Palmer; L. Brianna Caddle; Rachel Urban; Leslie O. Goodwin; Ian C. Welsh; Laura G. Reinholdt; David E. Bergstrom; Timothy C. Cox; Leah Rae Donahue; Stephen A. Murray (Mammalian Genome, 2023)

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Sediment gravity flow frequency offshore central California diminished significantly following the Last Glacial Maximum - Stephen C. Dobbs; Charles K. Paull; Eve M. Lundsten; Roberto Gwiazda; David W. Caress; Mary McGann; Marianne M. Coholich; Maureen A. L. Walton; Nora M. Nieminski; Tim McHargue; Stephan A. Graham (Frontiers in Marine Science, 2023)
A high-resolution multibeam survey from a portion of the San Simeon Channel (offshore Morro Bay, California) captured a zone of recurring troughs and ridges adjacent to prominent submarine meander bends. Through an integrated study using surveying data, sediment core analysis, radiocarbon dating, and stable isotope measurements, we hypothesize that turbidity current event frequency was higher during the late Pleistocene than at present conditions. We speculate that the rise in sea-level following the Last Glacial Maximum sequestered sedimentation largely to the shelf during the Holocene. This work suggests that the occurrence of sediment gravity flows in this region, particularly away from any submarine channels, is appreciably lower than at times of continental shelf subaerial exposure.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Hydrogeology of an urban weathered basement aquifer in Kampala, Uganda - Philip M. Nyenje; Denis Ocoromac; Stephen Tumwesige; Matt J. Ascott; James P. R. Sorensen; Andrew J. Newell; David M. J. Macdonald; Daren C. Gooddy; Callist Tindimugaya; Robinah N. Kulabako; Dan J. Lapworth; Jan Willem Foppen (Hydrogeology Journal, 2022)
Weathered basement aquifers are vital sources of drinking water in Africa. In order to better understand their role in the urban water balance, in a weathered basement aquifer in Kampala, Uganda, this study installed a transect of monitoring piezometers, carried out spring flow and high-frequency groundwater level monitoring, slug tests and hydrochemical analyses, including stable isotopes and groundwater residence time indicators. Findings showed a typical weathered basement aquifer with a 20–50-m thickness. Groundwater recharge was 3–50 mm/year, occurring during sustained rainfall. Recharge to a deep groundwater system within the saprock was slow and prolonged, while recharge to the springs on the valley slopes was quick and episodic, responding rapidly to precipitation. Springs discharged shallow groundwater, mixed with wastewater infiltrating from onsite sanitation practices and contributions from the deeper aquifer and were characterised by low flow rates (< 0.001 m 3 /s), low pH (<5), high nitrate values (61–190 mg/L as NO 3 ), and residence times of <30 years. The deeper groundwater system occurred in the saprolite/saprock, had low transmissivity (< 1 × 10 −5 m 2 /s), lower nitrate values (<20 mg/L as NO 3 ), pH 6–6.5 and longer residence times (40–60 years). Confined groundwater conditions in the valleys were created by the presence of clay-rich alluvium and gave rise to artesian conditions where groundwater had lower nitrate concentrations. The findings provide new insights into weathered basement aquifers in the urban tropics and show that small-scale abstractions are more sustainable in the deeper groundwater system in the valleys, where confined conditions are present.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Race reporting and disparities regarding clinical trials in bladder cancer: a systematic review - Elliott Freudenburg; Iyla Bagheri; Sunay Srinivas; Ariza Martinez; Nagireddy Putluri; Zachary Klaassen; Ashish M. Kamat; Badrinath R. Konety; William Y. Kim; Lars Dyrskjøt; David J. McConkey; Stephen J. Freedland; et al. (Cancer Causes & Control, 2022)

Rapid assessments of Pacific Ocean net coral reef carbonate budgets and net calcification following the 2014–2017 global coral bleaching event - Travis A. Courtney; Hannah C. Barkley; Stephen Chan; Courtney S. Couch; Tye L. Kindinger; Thomas A. Oliver; David J. Kriegman; Andreas J. Andersson (Limnology and Oceanography, 2022)
The 2014–2017 global coral bleaching event caused widespread coral mortality; however, its impact on the capacity for coral reefs to maintain calcium carbonate structures has not been determined. Here, we quantified remotely sensed maximum heat stress during the 2014–2017 bleaching event, census‐based net carbonate budgets from benthic imagery and fish survey data, and net reef calcification from salinity normalized seawater total alkalinity anomalies collected from 2017–2019 for 56 Pacific coral reef sites (Mariana Islands, Northwestern Hawaiian Islands, Pacific Remote Island Areas, and American Samoa). We incorporated the census‐based and chemistry‐based metrics to determine a calcification vulnerability index for each site to maintain calcium carbonate balance to provide accessible information to managers and policy makers. Most coral reef sites likely experienced ecologically severe (79%, n = 44) or significant (9%, n = 7) heat stress during the 2014–2017 coral bleaching event. Census‐based net carbonate budgets (mean ± 95% = 2.1 ± 0.6 kg CaCO 3 m −2 yr −1 ) were positive for 77% of sites ( n = 43), neutral for 16% of sites ( n = 9), and negative for 7% of sites ( n = 4). Chemistry‐based relative net reef calcification (mean ± 95% = 22 ± 10 μ mol kg −1 ) was positive for 84% of sites ( n = 47), neutral for 11% of sites ( n = 6), and negative for 5% of sites ( n = 3). The calcification vulnerability index suggested the Pacific Ocean reef sites surveyed were of minimal (68%, n = 38) to moderate (32%, n = 18) concern for maintaining calcium carbonate balance following the bleaching event. This suggests that many reefs maintained positive calcium carbonate balance, but that a large number of reefs may be approaching a potential threshold for maintaining their calcium carbonate balance under the climate crisis.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

A roadmap to integrating resilience into the practice of coral reef restoration - Elizabeth C. Shaver; Elizabeth McLeod; Margaux Y. Hein; Stephen R. Palumbi; Kate Quigley; Tali Vardi; Peter J. Mumby; David Smith; Phanor Montoya‐Maya; Erinn M. Muller; Anastazia T. Banaszak; Ian M. McLeod; et al. (Global Change Biology, 2022)
Recent warm temperatures driven by climate change have caused mass coral bleaching and mortality across the world, prompting managers, policymakers, and conservation practitioners to embrace restoration as a strategy to sustain coral reefs. Despite a proliferation of new coral reef restoration efforts globally and increasing scientific recognition and research on interventions aimed at supporting reef resilience to climate impacts, few restoration programs are currently incorporating climate change and resilience in project design. As climate change will continue to degrade coral reefs for decades to come, guidance is needed to support managers and restoration practitioners to conduct restoration that promotes resilience through enhanced coral reef recovery, resistance, and adaptation. Here, we address this critical implementation gap by providing recommendations that integrate resilience principles into restoration design and practice, including for project planning and design, coral selection, site selection, and broader ecosystem context. We also discuss future opportunities to improve restoration methods to support enhanced outcomes for coral reefs in response to climate change. As coral reefs are one of the most vulnerable ecosystems to climate change, interventions that enhance reef resilience will help to ensure restoration efforts have a greater chance of success in a warming world. They are also more likely to provide essential contributions to global targets to protect natural biodiversity and the human communities that rely on reefs.

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Gene arrangement, phylogeny and divergence time estimation of mitogenomes in Thrips - Avas Pakrashi; Vikas Kumar; David A. C. Stanford-Beale; Stephen L. Cameron; Kaomud Tyagi (Molecular Biology Reports, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Cancer and cardiovascular-related perceived risk in a diverse cancer center catchment area - Laura C. Pinheiro; Orysya Soroka; Dominic Razon; Rosio Ramos; Francesse Antoine; Andrew J. Dannenberg; Monika Safford; Stephen J. Peterson; Rulla M. Tamimi; David M. Nanus; Erica Phillips (Cancer Causes & Control, 2022)
Purpose Despite cancer and cardiovascular disease (CVD) sharing several modifiable risk factors, few unified prevention efforts exist. We sought to determine the association between risk perception for cancer and CVD and engagement in healthy behaviors. Methods Between May 2019 and August 2020, we conducted a cross-sectional survey of adults ≥ 40 years residing in Brooklyn neighborhoods with high cancer mortality. We considered one’s perceived risk of cancer and CVD compared to age counterparts as the primary exposures. The primary study outcome was a weighted health behavior score (wHBS) composed of 5 domains: physical activity, no obesity, no smoking, low alcohol intake, and healthy diet. Modified Poisson regression models with robust error variance were used to assess associations between perceived risk for cancer and CVD and the wHBS, separately. Results We surveyed 2448 adults (mean [SD] age, 61.4 [12.9] years); 61% female, 30% Non-Hispanic White, and 70% racial/ethnic minorities. Compared to their age counterparts nearly one-third of participants perceived themselves to be at higher CVD or cancer risk. Perceiving higher CVD risk was associated with an 8% lower likelihood of engaging in healthy behaviors (RR 0.92; 95% CI 0.86–0.99). Perceiving greater cancer risk was associated with a 14% lower likelihood of engaging in healthy behaviors (RR 0.86; 95% CI 0.79–0.95). The association between cancer risk and wHBS attenuated but remained significant (aRR 0.90; 95% CI 0.82–0.98) after adjustment. Conclusion Identifying high-risk subgroups and intervening on shared risk behaviors could have the greatest long-term impact on reducing CVD and cancer morbidity and mortality.

Estimating peanut and soybean photosynthetic traits using leaf spectral reflectance and advance regression models - Ma. Luisa Buchaillot; David Soba; Tianchu Shu; Juan Liu; Iker Aranjuelo; José Luis Araus; G. Brett Runion; Stephen A. Prior; Shawn C. Kefauver; Alvaro Sanz-Saez (Planta, 2022)
Main conclusion By combining hyperspectral signatures of peanut and soybean, we predicted V cmax and J max with 70 and 50% accuracy. The PLS was the model that better predicted these photosynthetic parameters. Abstract One proposed key strategy for increasing potential crop stability and yield centers on exploitation of genotypic variability in photosynthetic capacity through precise high-throughput phenotyping techniques. Photosynthetic parameters, such as the maximum rate of Rubisco catalyzed carboxylation ( V c ,max ) and maximum electron transport rate supporting RuBP regeneration ( J max ), have been identified as key targets for improvement. The primary techniques for measuring these physiological parameters are very time-consuming. However, these parameters could be estimated using rapid and non-destructive leaf spectroscopy techniques. This study compared four different advanced regression models (PLS, BR, ARDR, and LASSO) to estimate V c ,max and J max based on leaf reflectance spectra measured with an ASD FieldSpec4. Two leguminous species were tested under different controlled environmental conditions: (1) peanut under different water regimes at normal atmospheric conditions and (2) soybean under high [CO 2 ] and high night temperature. Model sensitivities were assessed for each crop and treatment separately and in combination to identify strengths and weaknesses of each modeling approach. Regardless of regression model, robust predictions were achieved for V c ,max ( R 2 = 0.70) and J max ( R 2 = 0.50). Field spectroscopy shows promising results for estimating spatial and temporal variations in photosynthetic capacity based on leaf and canopy spectral properties.

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Climate policy conflict in the U.S. states: a critical review and way forward - Joshua A. Basseches; Rebecca Bromley-Trujillo; Maxwell T. Boykoff; Trevor Culhane; Galen Hall; Noel Healy; David J. Hess; David Hsu; Rachel M. Krause; Harland Prechel; J. Timmons Roberts; Jennie C. Stephens (Climatic Change, 2022)
Many U.S. states have taken significant action on climate change in recent years, demonstrating their commitment despite federal policy gridlock and rollbacks. Yet, there is still much we do not know about the agents, discourses, and strategies of those seeking to delay or obstruct state-level climate action. We first ask, what are the obstacles to strong and effective climate policy within U.S. states? We review the political structures and interest groups that slow action, and we examine emerging tensions between climate justice and the technocratic and/or market-oriented approaches traditionally taken by many mainstream environmental groups. Second, what are potential solutions for overcoming these obstacles? We suggest strategies for overcoming opposition to climate action that may advance more effective and inclusive state policy, focusing on political strategies, media framing, collaboration, and leveraging the efforts of ambitious local governments.

Biogeochemical consequences of a changing Arctic shelf seafloor ecosystem - Christian März; Felipe S. Freitas; Johan C. Faust; Jasmin A. Godbold; Sian F. Henley; Allyson C. Tessin; Geoffrey D. Abbott; Ruth Airs; Sandra Arndt; David K. A. Barnes; Laura J. Grange; Neil D. Gray; et al. (Ambio, 2022)
Unprecedented and dramatic transformations are occurring in the Arctic in response to climate change, but academic, public, and political discourse has disproportionately focussed on the most visible and direct aspects of change, including sea ice melt, permafrost thaw, the fate of charismatic megafauna, and the expansion of fisheries. Such narratives disregard the importance of less visible and indirect processes and, in particular, miss the substantive contribution of the shelf seafloor in regulating nutrients and sequestering carbon. Here, we summarise the biogeochemical functioning of the Arctic shelf seafloor before considering how climate change and regional adjustments to human activities may alter its biogeochemical and ecological dynamics, including ecosystem function, carbon burial, or nutrient recycling. We highlight the importance of the Arctic benthic system in mitigating climatic and anthropogenic change and, with a focus on the Barents Sea, offer some observations and our perspectives on future management and policy.

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Correction to: A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)

A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)
There is great need for coordination around standards and best practices in neuroscience to support efforts to make neuroscience a data-centric discipline. Major brain initiatives launched around the world are poised to generate huge stores of neuroscience data. At the same time, neuroscience, like many domains in biomedicine, is confronting the issues of transparency, rigor, and reproducibility. Widely used, validated standards and best practices are key to addressing the challenges in both big and small data science, as they are essential for integrating diverse data and for developing a robust, effective, and sustainable infrastructure to support open and reproducible neuroscience. However, developing community standards and gaining their adoption is difficult. The current landscape is characterized both by a lack of robust, validated standards and a plethora of overlapping, underdeveloped, untested and underutilized standards and best practices. The International Neuroinformatics Coordinating Facility (INCF), an independent organization dedicated to promoting data sharing through the coordination of infrastructure and standards, has recently implemented a formal procedure for evaluating and endorsing community standards and best practices in support of the FAIR principles. By formally serving as a standards organization dedicated to open and FAIR neuroscience, INCF helps evaluate, promulgate, and coordinate standards and best practices across neuroscience. Here, we provide an overview of the process and discuss how neuroscience can benefit from having a dedicated standards body.

Quantifying fishing activity targeting subsea pipelines by commercial trap fishers - Todd Bond; Dianne L. McLean; Corey B. Wakefield; Julian C. Partridge; Jane Prince; David White; Dion K. Boddington; Stephen J. Newman (Reviews in Fish Biology and Fisheries, 2021)

From tides to nucleotides: Genomic signatures of adaptation to environmental heterogeneity in barnacles - Joaquin C. B. Nunez; Stephen Rong; David A. Ferranti; Alejandro Damian‐Serrano; Kimberly B. Neil; Henrik Glenner; Rebecca G. Elyanow; Bianca R. P. Brown; Magnus Alm Rosenblad; Anders Blomberg; Kerstin Johannesson; David M. Rand (Molecular Ecology, 2021)
The northern acorn barnacle ( Semibalanus balanoides ) is a robust system to study the genetic basis of adaptations to highly heterogeneous environments. Adult barnacles may be exposed to highly dissimilar levels of thermal stress depending on where they settle in the intertidal (i.e., closer to the upper or lower tidal boundary). For instance, barnacles near the upper tidal limit experience episodic summer temperatures above recorded heat coma levels. This differential stress at the microhabitat level is also dependent on the aspect of sun exposure. In the present study, we used pool‐seq approaches to conduct a genome wide screen for loci responding to intertidal zonation across the North Atlantic basin (Maine, Rhode Island, and Norway). Our analysis discovered 382 genomic regions containing SNPs which are consistently zonated (i.e., SNPs whose frequencies vary depending on their position in the rocky intertidal) across all surveyed habitats. Notably, most zonated SNPs are young and private to the North Atlantic. These regions show high levels of genetic differentiation across ecologically extreme microhabitats concomitant with elevated levels of genetic variation and Tajima's D , suggesting the action of non‐neutral processes. Overall, these findings support the hypothesis that spatially heterogeneous selection is a general and repeatable feature for this species, and that natural selection can maintain functional genetic variation in heterogeneous environments.

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Net design for selective control of the “plague minnow” Gambusia holbrooki that minimises impact on native Australian fishes - David L. Morgan; Karissa O. Lear; Brendan C. Ebner; Stephen J. Beatty (Journal of Fish Biology, 2021)
Gambusia holbrooki is one of the world's most environmentally damaging introduced species, being notoriously difficult to control once established. A composite double‐winged fyke net comprising four vertically stacked compartments was developed to determine the potential to control G. holbrooki , while reducing negative interactions of this aggressive species with small threatened fishes. The stacked fyke net captured three times as many G. holbrooki as a conventional fyke net while maintaining consistent catches of native fishes relative to that from a conventional fyke net, and detected species‐specific vertical distributions. This stratified net design represents a valuable management option for controlling this agonistic species or for limiting antagonistic interactions between G. holbrooki and native species during typical fyke sampling of native ecosystems.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

When hazard avoidance is not an option: lessons learned from monitoring the postdisaster Oso landslide, USA - Mark E. Reid; Jonathan W. Godt; Richard G. LaHusen; Stephen L. Slaughter; Thomas C. Badger; Brian D. Collins; William H. Schulz; Rex L. Baum; Jeffrey A. Coe; Edwin L. Harp; Kevin M. Schmidt; Richard M. Iverson; et al. (Landslides, 2021)
On 22 March 2014, a massive, catastrophic landslide occurred near Oso, Washington, USA, sweeping more than 1 km across the adjacent valley flats and killing 43 people. For the following 5 weeks, hundreds of workers engaged in an exhaustive search, rescue, and recovery effort directly in the landslide runout path. These workers could not avoid the risks posed by additional large-scale slope collapses. In an effort to ensure worker safety, multiple agencies cooperated to swiftly deploy a monitoring and alerting system consisting of sensors, automated data processing and web-based display, along with defined communication protocols and clear calls to action for emergency management and search personnel. Guided by the principle that an accelerating landslide poses a greater threat than a steadily moving or stationary mass, the system was designed to detect ground motion and vibration using complementary monitoring techniques. Near real-time information was provided by continuous GPS, seismometers/geophones, and extensometers. This information was augmented by repeat-assessment techniques such as terrestrial and aerial laser scanning and time-lapse photography. Fortunately, no major additional landsliding occurred. However, we did detect small headscarp failures as well as slow movement of the remaining landslide mass with the monitoring system. This was an exceptional response situation and the lessons learned are applicable to other landslide disaster crises. They underscore the need for cogent landslide expertise and ready-to-deploy monitoring equipment, the value of using redundant monitoring techniques with distinct goals, the benefit of clearly defined communication protocols, and the importance of continued research into forecasting landslide behavior to allow timely warning.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Penguins and Seals Transport Limiting Nutrients Between Offshore Pelagic and Coastal Regions of Antarctica Under Changing Sea Ice - Stephen R. Wing; Lucy C. Wing; Sorrel A. O’Connell-Milne; David Barr; Dale Stokes; Sal Genovese; James J. Leichter (Ecosystems, 2021)

Eriophyid mite Floracarus perrepae readily colonizes recovering invasive vine Lygodium microphyllum following herbicide treatment - Aaron S. David; Jonathan S. Glueckert; Stephen F. Enloe; Andrea Carmona Cortes; Anwar A. Abdel-Kader; Ellen C. Lake (BioControl, 2021)

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

Exploring controls of the early and stepped deglaciation on the western margin of the British Irish Ice Sheet - Sara Benetti; Richard C. Chiverrell; Colm Ó Cofaigh; Matt Burke; Alicia Medialdea; David Small; Colin Ballantyne; Mark D. Bateman; S. Louise Callard; Peter Wilson; Derek Fabel; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
New optically stimulated luminescence dating and Bayesian models integrating all legacy and BRITICE‐CHRONO geochronology facilitated exploration of the controls on the deglaciation of two former sectors of the British–Irish Ice Sheet, the Donegal Bay (DBIS) and Malin Sea ice‐streams (MSIS). Shelf‐edge glaciation occurred ~27 ka, before the global Last Glacial Maximum, and shelf‐wide retreat began 26–26.5 ka at a rate of ~18.7–20.7 m a –1 . MSIS grounding zone wedges and DBIS recessional moraines show episodic retreat punctuated by prolonged still‐stands. By ~23–22 ka the outer shelf (~25 000 km 2 ) was free of grounded ice. After this time, MSIS retreat was faster (~20 m a –1 vs. ~2–6 m a –1 of DBIS). Separation of Irish and Scottish ice sources occurred ~20–19.5 ka, leaving an autonomous Donegal ice dome. Inner Malin shelf deglaciation followed the submarine troughs reaching the Hebridean coast ~19 ka. DBIS retreat formed the extensive complex of moraines in outer Donegal Bay at 20.5–19 ka. DBIS retreated on land by ~17–16 ka. Isolated ice caps in Scotland and Ireland persisted until ~14.5 ka. Early retreat of this marine‐terminating margin is best explained by local ice loading increasing water depths and promoting calving ice losses rather than by changes in global temperatures. Topographical controls governed the differences between the ice‐stream retreat from mid‐shelf to the coast.

Timing and pace of ice‐sheet withdrawal across the marine–terrestrial transition west of Ireland during the last glaciation - Colm Ó Cofaigh; S. Louise Callard; David H. Roberts; Richard C. Chiverrell; C. K. Ballantyne; David J. A. Evans; Margot Saher; Katrien J. J. Van Landeghem; Rachel Smedley; Sara Benetti; Matthew Burke; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
Understanding the pace and drivers of marine‐based ice‐sheet retreat relies upon the integration of numerical ice‐sheet models with observations from contemporary polar ice sheets and well‐constrained palaeo‐glaciological reconstructions. This paper provides a reconstruction of the retreat of the last British–Irish Ice Sheet (BIIS) from the Atlantic shelf west of Ireland during and following the Last Glacial Maximum (LGM). It uses marine‐geophysical data and sediment cores dated by radiocarbon, combined with terrestrial cosmogenic nuclide and optically stimulated luminescence dating of onshore ice‐marginal landforms, to reconstruct the timing and rate of ice‐sheet retreat from the continental shelf and across the adjoining coastline of Ireland, thus including the switch from a marine‐ to a terrestrially‐based ice‐sheet margin. Seafloor bathymetric data in the form of moraines and grounding‐zone wedges on the continental shelf record an extensive ice sheet west of Ireland during the LGM which advanced to the outer shelf. This interpretation is supported by the presence of dated subglacial tills and overridden glacimarine sediments from across the Porcupine Bank, a westwards extension of the Irish continental shelf. The ice sheet was grounded on the outer shelf at ~26.8 ka cal bp with initial retreat underway by 25.9 ka cal bp. Retreat was not a continuous process but was punctuated by marginal oscillations until ~24.3 ka cal bp. The ice sheet thereafter retreated to the mid‐shelf where it formed a large grounding‐zone complex at ~23.7 ka cal bp. This retreat occurred in a glacimarine environment. The Aran Islands on the inner continental shelf were ice‐free by ~19.5 ka bp and the ice sheet had become largely terrestrially based by 17.3 ka bp. This suggests that the Aran Islands acted to stabilize and slow overall ice‐sheet retreat once the BIIS margin had reached the inner shelf. Our results constrain the timing of initial retreat of the BIIS from the outer shelf west of Ireland to the period of minimum global eustatic sea level. Initial retreat was driven, at least in part, by glacio‐isostatically induced, high relative sea level. Net rates of ice‐sheet retreat across the shelf were slow (62–19 m a −1 ) and reduced (8 m a −1 ) as the ice sheet vacated the inner shelf and moved onshore. A picture therefore emerges of an extensive BIIS on the Atlantic shelf west of Ireland, in which early, oscillatory retreat was followed by slow episodic retreat which decelerated further as the ice margin became terrestrially based. More broadly, this demonstrates the importance of localized controls, in particular bed topography, on modulating the retreat of marine‐based sectors of ice sheets.

Controls on Nutrient Cycling in Estuarine Mangrove Lake Sediments - Michael S. Owens; Stephen P. Kelly; Thomas A. Frankovich; David T. Rudnick; James W. Fourqurean; Jeffrey C. Cornwell (Journal of Marine Science and Engineering, 2021)
We estimated the net exchange of nitrogen and phosphorus species using core incubations under light and dark conditions in estuarine lakes that are the aquatic interface between the freshwater Everglades and marine Florida Bay. These lakes and adjacent shallow water Florida Bay environments are sites where the restoration of hydrological flows will likely have the largest impact on salinity. Sediment respiration, measured by oxygen uptake, averaged (±S.D.) −2400 ± 1300, −300 ± 1000, and 1900 ± 1400 μmol m−2 h−1 for dark incubations, light incubations, and gross photosynthesis estimates, respectively, with dark incubations consistent with oxygen uptake measured by microelectrode profiles. Although most fluxes of soluble reactive phosphorus, nitrate, and N2–N were low under both light and dark incubation conditions, we observed a number of very high efflux events of NH4+ during dark incubations. A significant decrease in NH4+flux was observed in the light. The largest differences between light and dark effluxes of NH4+ occurred in lakes during periods of low coverage of the aquatic macrophyte Chara hornemannii Wallman, with NH4+ effluxes > 200 μmol m−2 h−1. Increasing freshwater flow from the Everglades is expected to expand lower salinity environments suitable for Chara, and therefore, diminish the sediment NH4+ effluxes that may fuel algal blooms.

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

Forest responses to last‐millennium hydroclimate variability are governed by spatial variations in ecosystem sensitivity - Christine R. Rollinson; Andria Dawson; Ann M. Raiho; John W. Williams; Michael C. Dietze; Thomas Hickler; Stephen T. Jackson; Jason McLachlan; David JP Moore; Benjamin Poulter; Tristan Quaife; Jörg Steinkamp; et al. (Ecology Letters, 2021)
Forecasts of future forest change are governed by ecosystem sensitivity to climate change, but ecosystem model projections are under‐constrained by data at multidecadal and longer timescales. Here, we quantify ecosystem sensitivity to centennial‐scale hydroclimate variability, by comparing dendroclimatic and pollen‐inferred reconstructions of drought, forest composition and biomass for the last millennium with five ecosystem model simulations. In both observations and models, spatial patterns in ecosystem responses to hydroclimate variability are strongly governed by ecosystem sensitivity rather than climate exposure. Ecosystem sensitivity was higher in models than observations and highest in simpler models. Model‐data comparisons suggest that interactions among biodiversity, demography and ecophysiology processes dampen the sensitivity of forest composition and biomass to climate variability and change. Integrating ecosystem models with observations from timescales extending beyond the instrumental record can better understand and forecast the mechanisms regulating forest sensitivity to climate variability in a complex and changing world.

Assessing the impact of taxon resolution on network structure - David R. Hemprich‐Bennett; Hernani F. M. Oliveira; Steven C. Le Comber; Stephen J. Rossiter; Elizabeth L. Clare (Ecology, 2021)
Constructing ecological networks has become an indispensable approach in understanding how different taxa interact. However, the methods used to generate data in network research vary widely among studies, potentially limiting our ability to compare results meaningfully. In particular, methods of classifying nodes vary in their precision, likely altering the architecture of the network studied. For example, rather than being classified as Linnaean species, taxa are regularly assigned to morphospecies in observational studies, or to molecular operational taxonomic units (MOTUs) in molecular studies, with the latter defined based on an arbitrary threshold of sequence similarity. Although the use of MOTUs in ecological networks holds great potential, especially for allowing rapid construction of large data sets of interactions, it is unclear how the choice of clustering threshold can influence the conclusions obtained. To test the impact of taxonomic precision on network architecture, we obtained and analyzed 16 data sets of ecological interactions, inferred from metabarcoding and observations. Our comparisons of networks constructed under a range of sequence thresholds for assigning taxa demonstrate that even small changes in node resolution can cause wide variation in almost all key metric values. Moreover, relative values of commonly used metrics such as robustness were seen to fluctuate continuously with node resolution, thereby potentially causing error in conclusions drawn when comparing multiple networks. In observational networks, we found that changing node resolution could, in some cases, lead to substantial changes to measurements of network topology. Overall, our findings highlight the importance of classifying nodes to the greatest precision possible, and demonstrate the need for caution when comparing networks that differ with respect to node resolution, even where taxonomic groups and interaction types are similar. In such cases, we recommend that comparisons of networks should focus on relative differences rather than absolute values between the networks studied.

Can crown variables increase the generality of individual tree biomass equations? - David I. Forrester; Ian C. Dumbrell; Stephen R. Elms; Keryn I. Paul; Elizabeth A. Pinkard; Stephen H. Roxburgh; Thomas G. Baker (Trees, 2021)

Predictors of invertebrate biomass and rate of advancement of invertebrate phenology across eight sites in the North American Arctic - Rebecca Shaftel; Daniel J. Rinella; Eunbi Kwon; Stephen C. Brown; H. River Gates; Steve Kendall; David B. Lank; Joseph R. Liebezeit; David C. Payer; Jennie Rausch; Sarah T. Saalfeld; Brett K. Sandercock; et al. (Polar Biology, 2021)
Average annual temperatures in the Arctic increased by 2–3 °C during the second half of the twentieth century. Because shorebirds initiate northward migration to Arctic nesting sites based on cues at distant wintering grounds, climate-driven changes in the phenology of Arctic invertebrates may lead to a mismatch between the nutritional demands of shorebirds and the invertebrate prey essential for egg formation and subsequent chick survival. To explore the environmental drivers affecting invertebrate availability, we modeled the biomass of invertebrates captured in modified Malaise-pitfall traps over three summers at eight Arctic Shorebird Demographics Network sites as a function of accumulated degree-days and other weather variables. To assess climate-driven changes in invertebrate phenology, we used data from the nearest long-term weather stations to hindcast invertebrate availability over 63 summers, 1950–2012. Our results confirmed the importance of both accumulated and daily temperatures as predictors of invertebrate availability while also showing that wind speed negatively affected invertebrate availability at the majority of sites. Additionally, our results suggest that seasonal prey availability for Arctic shorebirds is occurring earlier and that the potential for trophic mismatch is greatest at the northernmost sites, where hindcast invertebrate phenology advanced by approximately 1–2.5 days per decade. Phenological mismatch could have long-term population-level effects on shorebird species that are unable to adjust their breeding schedules to the increasingly earlier invertebrate phenologies.

A Synthesis of the Biology and Ecology of Sculpin Species in the Laurentian Great Lakes and Implications for the Adaptive Capacity of the Benthic Ecosystem - Kelly F. Robinson; Charles R. Bronte; David B. Bunnell; Peter T. Euclide; Darryl W. Hondorp; John A. Janssen; Matthew S. Kornis; Derek H. Ogle; Will Otte; Stephen C. Riley; Mark R. Vinson; Shea L. Volkel; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Shallow groundwater flow and inverted fresh/saline-water interface in a hypersaline endorheic basin (Great Basin, USA) - Alan L. Mayo; David G. Tingey; Kevin A. Rey; Tony D. Winkel; John H. McBride; Stephen T. Nelson; Gregory T. Carling; Jiri Bruthans; Erik C. Petersen (Hydrogeology Journal, 2020)
Pilot Valley is an 828-km 2 arid-region endorheic basin in western USA. Bounding mountain ranges rise as much as 1,900 m above the nearly flat 379-km 2 playa floor. Up to 3.8 m of Pleistocene Lake Bonneville mud and thin oolitic sand layers form the surface layer of the basin floor. Groundwater conditions were evaluated using data from shallow monitoring wells and borings, springs, infiltrometer measurements, slug and dilution tests, geophysical transects, and precision elevation surveys. Alluvial fan groundwater discharges at fan/playa interface springs and underflows to the shallow basin sediments along the western side of the basin; the groundwater only underflows along the eastern side. Precision surveying established a Lake Bonneville shore-line break in slope as the cause of the spring discharges. Tectonic tilting causes groundwater to flow from east to west and to the topographic low. Monthly measured and pressure transducer data established seasonal pressure responses and upward groundwater gradients. All basin groundwater is lost to evapotranspiration at the topographic low, where a thin salt pan has developed. Groundwater evolves from fresh to hypersaline near the alluvial fan/playa interface where there is an inverted salinity gradient and a groundwater pressure ridge. The pressure ridge and inverted salinity interface are due to: (1) osmotic pressure established between the oolitic sand of high hydraulic conductivity and the overlying low-hydraulic-conductivity lake mud at the fan/playa interface, and (2) the collision between fresh groundwater flow driven by a steep hydraulic head and hypersaline groundwater flow driven by a nearly flat hydraulic head.

Co-administration of Selenium Nanoparticles and Metformin Abrogate Testicular Oxidative Injury by Suppressing Redox Imbalance, Augmenting Sperm Quality and Nrf2 Protein Expression in Streptozotocin-Induced Diabetic Rats - Azubuike P. Ebokaiwe; Kebe E. Obeten; Stephen O. Okori; Ebuka E. David; Olasehinde Olusanya; Chukwuma J. Chukwu; Nworie Okoro; Richard C. Ehiri (Biological Trace Element Research, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Rapid Assessment of Wetland Condition Reflects Amphibian Community Composition - Kari Dupler; Michelle Guidugli-Cook; David R. Brown; Stephen C. Richter (Wetlands, 2020)

Divergent field metabolic rates highlight the challenges of increasing temperatures and energy limitation in aquatic ectotherms - Karissa O. Lear; David L. Morgan; Jeff M. Whitty; Nicholas M. Whitney; Evan E. Byrnes; Stephen J. Beatty; Adrian C. Gleiss (Oecologia, 2020)

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Climatic vulnerabilities and ecological preferences of soil invertebrates across biomes - Felipe Bastida; David J. Eldridge; Sebastián Abades; Fernando D. Alfaro; Antonio Gallardo; Laura García‐Velázquez; Carlos García; Stephen C. Hart; Cecilia A. Pérez; Fernanda Santos; Pankaj Trivedi; Mark A. Williams; et al. (Molecular Ecology, 2020)
Unlike plants and vertebrates, the ecological preferences, and potential vulnerabilities of soil invertebrates to environmental change, remain poorly understood in terrestrial ecosystems globally. We conducted a cross‐biome survey including 83 locations across six continents to advance our understanding of the ecological preferences and vulnerabilities of the diversity of dominant and functionally important soil invertebrate taxa, including nematodes, arachnids and rotifers. The diversity of invertebrates was analyzed through amplicon sequencing. Vegetation and climate drove the diversity and dominant taxa of soil invertebrates. Our results suggest that declines in forest cover and plant diversity, and reductions in plant production associated with increases in aridity, can result in reductions of the diversity of soil invertebrates in a drier and more managed world. We further developed global atlases of the diversity of these important soil invertebrates, which were cross‐validated using an independent database. Our study advances the current knowledge of the ecological preferences and vulnerabilities of the diversity and presence of functionally important soil invertebrates in soils from across the globe. This information is fundamental for improving and prioritizing conservation efforts of soil genetic resources and management policies.

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.

Coenzyme Q10 Alleviates Chronic Nucleoside Reverse Transcriptase Inhibitor-Induced Premature Endothelial Senescence - Yi-Fan Chen; Valeria Y. Hebert; Krisztian Stadler; Stephen Y. Xue; Kate Slaybaugh; Elliot Luttrell-Williams; Mitzi C. Glover; David M. Krzywanski; Tammy R. Dugas (Cardiovascular Toxicology, 2019)

Are Current Seedling Demographics Poised to Regenerate Northern US Forests? - Lance A Vickers; William H McWilliams; Benjamin O Knapp; Anthony W D’Amato; Daniel C Dey; Yvette L Dickinson; John M Kabrick; Laura S Kenefic; Christel C Kern; David R Larsen; Alejandro A Royo; Michael R Saunders; et al. (Journal of Forestry, 2019)
Securing desirable regeneration is essential to sustainable forest management, yet failures are common. Detailed seedling measurements from a forest inventory across 24 northern US states were examined for plausible regeneration outcomes following overstory removal. The examination included two fundamental regeneration objectives: 1) stand replacement- securing future forest and 2) species maintenance- securing upper canopy species. Almost half the plots lacked adequate seedlings to regenerate a stand after canopy removal and over half risked compositional shifts. Based on those advance reproduction demographics, regeneration difficulties could occur on two-thirds of the plots examined. The remaining one-third were regeneration-ready. However, compared to historical norms, increased small-tree mortality rates reduces that proportion. Not all forest types rely on advance reproduction and results varied among the forest types examined. Some variability was associated with browsing intensity, as areas of high deer browsing had a lower proportion of regeneration-ready plots.

Coral Reef Monitoring, Reef Assessment Technologies, and Ecosystem-Based Management - David O. Obura; Greta Aeby; Natchanon Amornthammarong; Ward Appeltans; Nicholas Bax; Joe Bishop; Russell E. Brainard; Samuel Chan; Pamela Fletcher; Timothy A. C. Gordon; Lew Gramer; Mishal Gudka; et al. (Frontiers in Marine Science, 2019)

Distribution of contaminants in the environment and wildlife habitat use: a case study with lead and waterfowl on the Upper Texas Coast - Brian Kearns; Stephen McDowell; Jena Moon; Elizabeth Rigby; Warren C. Conway; David Haukos (Ecotoxicology, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Molecular identification of Botryosphaeria dothidea as a fungal associate of the gall midge Asphondylia prosopidis on mesquite in the United States - Ikju Park; Soum Sanogo; Stephen F. Hanson; David C. Thompson (BioControl, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Better estimates of soil carbon from geographical data: a revised global approach - Sandra Duarte-Guardia; Pablo L. Peri; Wulf Amelung; Douglas Sheil; Shawn W. Laffan; Nils Borchard; Michael I. Bird; Wouter Dieleman; David A. Pepper; Brian Zutta; Esteban Jobbagy; Lucas C. R. Silva; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Developmental origins of pregnancy-induced cardiac changes: establishment of a novel model using the atrial natriuretic peptide gene-disrupted mice - Nicole M. Ventura; Terry Y. Li; M. Yat Tse; Logan Richard; Chandrakant Tayade; Albert Y. Jin; R. David Andrew; Stephen C. Pang (Molecular and Cellular Biochemistry, 2018)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Hierarchies of evolutionary radiation in the world’s most species rich vertebrate group, the Neotropical Pristimantis leaf litter frogs - Emily H. Waddell; Marco Crotti; Stephen C. Lougheed; David C. Cannatella; Kathryn R. Elmer (Systematics and Biodiversity, 2018)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Physical and chemical impacts of a major storm on a temperate lake: a taste of things to come? - R. Iestyn Woolway; John H. Simpson; David Spiby; Heidrun Feuchtmayr; Ben Powell; Stephen C. Maberly (Climatic Change, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Under what circumstances does the capture and tagging of wild Atlantic salmon Salmo salar smolts affect probability of return as adults? - William D. Riley; Anton T. Ibbotson; Stephen D. Gregory; Ian C. Russell; Rasmus B. Lauridsen; William R. C. Beaumont; Alastair C. Cook; David L. Maxwell (Journal of Fish Biology, 2018)
Adult return rates for wild Atlantic salmon Salmo salar smolts captured in a rotary screw trap and tagged with coded wire (CW) tags were compared with a control group, using detections from passive integrated transponder (PIT) antennae systems over 7 years in a small chalk stream in southern England, U.K. Compared with control smolts, capture and CW‐tagging of experimental smolts affected detected return rates only under certain conditions, with a decreased return probability for smolts caught and tagged following mild winter river temperature anomalies and during the night. Similarly, analysis of the experimental smolts revealed that capture and CW‐tagging following mild winters decreased their probability of return as adults. There were also marginal positive effects of length at PIT‐tagging as parr and length at CW‐tagging as smolts, on individual probability of return as adult. The results support the hypothesis that the effect of procedures involving the capture and tagging of migrating wild S. salar smolts will vary with the circumstances under which they are performed. The implications of the findings are considered in the context of ongoing investigations to derive and report marine return rates for S. salar in support of national and international stock assessments and in developing best practice.

Remotely sensed canopy nitrogen correlates with nitrous oxide emissions in a lowland tropical rainforest - Fiona M. Soper; Benjamin W. Sullivan; Megan K. Nasto; Brooke B. Osborne; David Bru; Christopher S. Balzotti; Phillip G. Taylor; Gregory P. Asner; Alan R. Townsend; Laurent Philippot; Stephen Porder; Cory C. Cleveland (Ecology, 2018)
Tropical forests exhibit significant heterogeneity in plant functional and chemical traits that may contribute to spatial patterns of key soil biogeochemical processes, such as carbon storage and greenhouse gas emissions. Although tropical forests are the largest ecosystem source of nitrous oxide (N 2 O), drivers of spatial patterns within forests are poorly resolved. Here, we show that local variation in canopy foliar N, mapped by remote‐sensing image spectroscopy, correlates with patterns of soil N 2 O emission from a lowland tropical rainforest. We identified ten 0.25 ha plots (assemblages of 40–70 individual trees) in which average remotely‐sensed canopy N fell above or below the regional mean. The plots were located on a single minimally‐dissected terrace ( 2 ) where soil type, vegetation structure and climatic conditions were relatively constant. We measured N 2 O fluxes monthly for 1 yr and found that high canopy N species assemblages had on average three‐fold higher total mean N 2 O fluxes than nearby lower canopy N areas. These differences are consistent with strong differences in litter stoichiometry, nitrification rates and soil nitrate concentrations. Canopy N status was also associated with microbial community characteristics: lower canopy N plots had two‐fold greater soil fungal to bacterial ratios and a significantly lower abundance of ammonia‐oxidizing archaea, although genes associated with denitrification ( nirS, nirK, nosZ ) showed no relationship with N 2 O flux. Overall, landscape emissions from this ecosystem are at the lowest end of the spectrum reported for tropical forests, consist with multiple metrics indicating that these highly productive forests retain N tightly and have low plant‐available losses. These data point to connections between canopy and soil processes that have largely been overlooked as a driver of denitrification. Defining relationships between remotely‐sensed plant traits and soil processes offers the chance to map these processes at large scales, potentially increasing our ability to predict N 2 O emissions in heterogeneous landscapes.

Risk of diabetes complications among those with diabetes receiving androgen deprivation therapy for localized prostate cancer - Marie C. Bradley; Yingjun Zhou; Andrew N. Freedman; Marianne Ulcickas Yood; Charles P. Quesenbery; Reina Haque; Stephen K. Van Den Eeden; Andrea E. Cassidy-Bushrow; David Aaronson; Arnold L. Potosky (Cancer Causes & Control, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Progress in designing and delivering effective fishing industry–science data collection in the UK - Stephen C Mangi; Sven Kupschus; Steven Mackinson; Dale Rodmell; Alexandra Lee; Elizabeth Bourke; Tom Rossiter; Jim Masters; Stuart Hetherington; Thomas Catchpole; David Righton (Fish and Fisheries, 2018)
This study was undertaken to address the increasing need for a strategic approach to industry–science data collections in the face of reducing resources and growing need for evidence in fisheries management. The aim was to evaluate progress in the development of plans and procedures that can be employed to collect, record and use fishing industry knowledge and data in the evidence base for managing fisheries. This was achieved by reviewing industry‐led data initiatives already undertaken or ongoing within the United Kingdom to document how these projects have/are incorporating fishing industry data into the process of management decision‐making; canvassing stakeholder opinion on data gaps and whether these could be filled by data gathered by commercial fishing vessels; establishing what issues might prevent or stimulate commercial fishing vessels in collecting data when they have the opportunity; and describing guidance on a step‐by‐step process for gathering scientific information such that fishers are empowered to collect the right data, at the right times and in the right format for their fishery. Given recent advances in the collection, interpretation and application of fisheries‐dependent data, we compare progress made in the UK to other areas of the world. We conclude that there is considerable evidence of a paradigm shift from the conventional practice of scientists asking fishers to provide data for scientific analyses towards full engagement of key stakeholders in data collection.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Chronic Remote Ischemic Conditioning Is Cerebroprotective and Induces Vascular Remodeling in a VCID Model - Mohammad Badruzzaman Khan; Sherif Hafez; Md. Nasrul Hoda; Babak Baban; Jesse Wagner; Mohamed E. Awad; Hasith Sangabathula; Stephen Haigh; Mohammed Elsalanty; Jennifer L. Waller; David C. Hess (Translational Stroke Research, 2018)

Climate change impacts on the conservation outlook of populations on the poleward periphery of species ranges: A case study of Canadian black‐tailed prairie dogs ( Cynomys ludovicianus ) - Tara Stephens; Sian C. Wilson; Ffion Cassidy; Darren Bender; David Gummer; Des H. V. Smith; Natasha Lloyd; Jana M. McPherson; Axel Moehrenschlager (Global Change Biology, 2018)
Given climate change, species' climatically suitable habitats are increasingly expected to shift poleward. Some imperilled populations towards the poleward edge of their species' range might therefore conceivably benefit from climate change. Interactions between climate and population dynamics may be complex, however, with climate exerting effects both indirectly via influence over food availability and more directly, via effects on physiology and its implications for survival and reproduction. A thorough understanding of these interactions is critical for effective conservation management. We therefore examine the relationship between climate, survival and reproduction in Canadian black‐tailed prairie dogs, a threatened keystone species in an imperilled ecosystem at the northern edge of the species' range. Our analyses considered 8 years of annual mark–recapture data (2007–2014) in relation to growing degree days, precipitation, drought status and winter severity, as well as year, sex, age and body mass. Survival was strongly influenced by the interaction of drought and body mass class, and winter temperature severity. Female reproductive status was associated with the interaction of growing degree days and growing season precipitation, with spring precipitation and with winter temperature severity. Results related to body mass suggested that climatic variables exerted their effects via regulation of food availability with potential linked effects of food quality, immunological and behavioural implications, and predation risk. Predictions of future increases in drought conditions in North America's grassland ecosystems have raised concerns for the outlook of Canadian black‐tailed prairie dogs. Insights gained from the analyses, however, point to mitigating species management options targeted at decoupling the mechanisms by which climate exerts its negative influence. Our approach highlights the importance of understanding the interaction between climate and population dynamics in peripheral populations whose viability might ultimately determine their species' ability to track climatically suitable space.

Energetic requirements of green sturgeon (Acipenser medirostris) feeding on burrowing shrimp (Neotrypaea californiensis) in estuaries: importance of temperature, reproductive investment, and residence time - Joshua M. Borin; Mary L. Moser; Adam G. Hansen; David A. Beauchamp; Stephen C. Corbett; Brett R. Dumbauld; Casey Pruitt; Jennifer L. Ruesink; Cinde Donoghue (Environmental Biology of Fishes, 2017)

No evidence for ecological segregation protecting native trout from invasive hybridization - Ryan P. Kovach; Clint C. Muhlfeld; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)

Legacy introductions and climatic variation explain spatiotemporal patterns of invasive hybridization in a native trout - Clint C. Muhlfeld; Ryan P. Kovach; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)
Hybridization between invasive and native species, a significant threat to worldwide biodiversity, is predicted to increase due to climate‐induced expansions of invasive species. Long‐term research and monitoring are crucial for understanding the ecological and evolutionary processes that modulate the effects of invasive species. Using a large, multidecade genetics dataset ( N = 582 sites, 12,878 individuals) with high‐resolution climate predictions and extensive stocking records, we evaluate the spatiotemporal dynamics of hybridization between native cutthroat trout and invasive rainbow trout, the world's most widely introduced invasive fish, across the Northern Rocky Mountains of the United States. Historical effects of stocking and contemporary patterns of climatic variation were strongly related to the spread of hybridization across space and time. The probability of occurrence, extent of, and temporal changes in hybridization increased at sites in close proximity to historical stocking locations with greater rainbow trout propagule pressure, warmer water temperatures, and lower spring precipitation. Although locations with warmer water temperatures were more prone to hybridization, cold sites were not protected from invasion; 58% of hybridized sites had cold mean summer water temperatures (

Field-based assessment of wetland condition, wetland extent, and the National Wetlands Inventory in Kentucky, USA - Michelle Guidugli-Cook; Stephen C. Richter; Barbara J. Scott; David R. Brown (Wetlands Ecology and Management, 2017)

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

Tracking reveals limited interactions between Campbell Albatross and fisheries during the breeding season - Lisa A. Sztukowski; Mariëlle L. van Toor; Henri Weimerskirch; David R. Thompson; Leigh G. Torres; Paul M. Sagar; Peter A. Cotton; Stephen C. Votier (Journal of Ornithology, 2017)

Genetic associations with lipoprotein subfraction measures differ by ethnicity in the multi-ethnic study of atherosclerosis (MESA) - Zhe Wang; Ani Manichukal; David C. Goff; Samia Mora; Jose M. Ordovas; Nicholas M. Pajewski; Wendy S. Post; Jerome I. Rotter; Michele M. Sale; Stephanie A. Santorico; David Siscovick; Michael Y. Tsai; et al. (Human Genetics, 2017)

Toward reassessing data‐deficient species - Lucie M. Bland; Jon Bielby; Stephen Kearney; C. David L. Orme; James E. M. Watson; Ben Collen (Conservation Biology, 2017)
One in 6 species (13,465 species) on the International Union for Conservation of Nature (IUCN) Red List is classified as data deficient due to lack of information on their taxonomy, population status, or impact of threats. Despite the chance that many are at high risk of extinction, data‐deficient species are typically excluded from global and local conservation priorities, as well as funding schemes. The number of data‐deficient species will greatly increase as the IUCN Red List becomes more inclusive of poorly known and speciose groups. A strategic approach is urgently needed to enhance the conservation value of data‐deficient assessments. To develop this, we reviewed 2879 data‐deficient assessments in 6 animal groups and identified 8 main justifications for assigning data‐deficient status (type series, few records, old records, uncertain provenance, uncertain population status or distribution, uncertain threats, taxonomic uncertainty, and new species). Assigning a consistent set of justification tags (i.e., consistent assignment to assessment justifications) to species classified as data deficient is a simple way to achieve more strategic assessments. Such tags would clarify the causes of data deficiency; facilitate the prediction of extinction risk; facilitate comparisons of data deficiency among taxonomic groups; and help prioritize species for reassessment. With renewed efforts, it could be straightforward to prevent thousands of data‐deficient species slipping unnoticed toward extinction.

An upstream migration fought with danger: freshwater sawfish fending off sharks and crocodiles - David L. Morgan; Ruchira Somaweera; Adrian C. Gleiss; Stephen J. Beatty; Jeff M. Whitty (Ecology, 2017)

Blueprints of Effective Biodiversity and Conservation Knowledge Products That Support Marine Policy - Lauren V. Weatherdon; Ward Appeltans; Nadine Bowles-Newark; Thomas M. Brooks; Frances E. Davis; Katherine Despot-Belmonte; Stephen Fletcher; Cristina Garilao; Craig Hilton-Taylor; Tim Hirsch; Diego Juffe-Bignoli; Kristin Kaschner; et al. (Frontiers in Marine Science, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Genome‐wide association of functional traits linked with C ampylobacter jejuni survival from farm to fork - Koji Yahara; Guillaume Méric; Aidan J. Taylor; Stefan P. W. de Vries; Susan Murray; Ben Pascoe; Leonardos Mageiros; Alicia Torralbo; Ana Vidal; Anne Ridley; Sho Komukai; Helen Wimalarathna; et al. (Environmental Microbiology, 2017)
Summary Campylobacter jejuni is a major cause of bacterial gastroenteritis worldwide, primarily associated with the consumption of contaminated poultry. C. jejuni lineages vary in host range and prevalence in human infection, suggesting differences in survival throughout the poultry processing chain. From 7343 MLST‐characterised isolates, we sequenced 600 C. jejuni and C. coli isolates from various stages of poultry processing and clinical cases. A genome‐wide association study (GWAS) in C. jejuni ST‐21 and ST‐45 complexes identified genetic elements over‐represented in clinical isolates that increased in frequency throughout the poultry processing chain. Disease‐associated SNPs were distinct in these complexes, sometimes organised in haplotype blocks. The function of genes containing associated elements was investigated, demonstrating roles for cj1377c in formate metabolism, nuoK in aerobic survival and oxidative respiration, and cj1368‐70 in nucleotide salvage. This work demonstrates the utility of GWAS for investigating transmission in natural zoonotic pathogen populations and provides evidence that major C. jejuni lineages have distinct genotypes associated with survival, within the host specific niche, from farm to fork.

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Enhancing conservation of A ustralian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences - Brendan C Ebner; David L Morgan; Adam Kerezsy; Scott Hardie; Stephen J Beatty; Jamie E Seymour; James A Donaldson; Simon Linke; Stirling Peverell; David Roberts; Thomas Espinoza; Nadine Marshall; et al. (Fish and Fisheries, 2016)
Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.

Stable isotopes and mtDNA reveal niche segregation but no evidence of intergradation along a habitat gradient in the Lesser Whitethroat complex (Sylvia curruca; Passeriformes; Aves) - Stephen C. Votier; Simon Aspinall; Stuart Bearhop; David Bilton; Jason Newton; Per Alström; Paul Leader; Geoff Carey; Robert W. Furnes; Urban Olsson (Journal of Ornithology, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Editorial - Stephen C. Bowden; David W. Loring (Neuropsychology Review, 2016)

A temperature-sensitive allele of a putative mRNA splicing helicase down-regulates many cell wall genes and causes radial swelling in Arabidopsis thaliana - Paul A. Howles; Leigh K. Gebbie; David A. Collings; Arvind Varsani; Ronan C. Broad; Stephen Ohms; Rosemary J. Birch; Ann H. Cork; Tony Arioli; Richard E. Williamson (Plant Molecular Biology, 2016)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Editorial - David W. Loring; Stephen C. Bowden (Neuropsychology Review, 2016)

Farm gate level nitrogen balance and use efficiency changes post implementation of the EU Nitrates Directive - Cathal Buckley; David P. Wall; Brian Moran; Stephen O’Neill; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2016)

Exploring, exploiting and evolving diversity of aquatic ecosystem models: a community perspective - Annette B. G. Janssen; George B. Arhonditsis; Arthur Beusen; Karsten Bolding; Louise Bruce; Jorn Bruggeman; Raoul-Marie Couture; Andrea S. Downing; J. Alex Elliott; Marieke A. Frassl; Gideon Gal; Daan J. Gerla; et al. (Aquatic Ecology, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Maternal hypertension programs increased cerebral tissue damage following stroke in adult offspring - Nicole M. Ventura; Albert Y. Jin; M. Yat Tse; Nichole T. Peterson; R. David Andrew; Jeffrey D. Mewburn; Stephen C. Pang (Molecular and Cellular Biochemistry, 2015)

High-resolution physical and biogeochemical variability from a shallow back reef on Ofu, American Samoa: an end-member perspective - David A. Koweek; Robert B. Dunbar; Stephen G. Monismith; David A. Mucciarone; C. Brock Woodson; Lianna Samuel (Coral Reefs, 2015)

Advancing Product Quality: a Summary of the Inaugural FDA/PQRI Conference - Lawrence X. Yu; Jeffrey Baker; Susan C. Berlam; Ashley Boam; E. J. Brandreth; Lucinda Buhse; Thomas Cosgrove; David Doleski; Lynne Ensor; Joseph Famulare; Mohan Ganapathy; Gustavo Grampp; et al. (The AAPS Journal, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Diversity and bioprospection of fungal community present in oligotrophic soil of continental Antarctica - Valéria M. Godinho; Vívian N. Gonçalves; Iara F. Santiago; Hebert M. Figueredo; Gislaine A. Vitoreli; Carlos E. G. R. Schaefer; Emerson C. Barbosa; Jaquelline G. Oliveira; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; Silvane M. F. Murta; et al. (Extremophiles, 2015)

Temporal patterns in adult salmon migration timing across southeast Alaska - Ryan P. Kovach; Stephen C. Ellison; Sanjay Pyare; David A. Tallmon (Global Change Biology, 2015)
Pacific salmon migration timing can drive population productivity, ecosystem dynamics, and human harvest. Nevertheless, little is known about long‐term variation in salmon migration timing for multiple species across broad regions. We used long‐term data for five Pacific salmon species throughout rapidly warming southeast Alaska to describe long‐term changes in salmon migration timing, interannual phenological synchrony, relationships between climatic variation and migratory timing, and to test whether long‐term changes in migration timing are related to glaciation in headwater streams. Temporal changes in the median date of salmon migration timing varied widely across species. Most sockeye populations are migrating later over time (11 of 14), but pink, chum, and especially coho populations are migrating earlier than they did historically (16 of 19 combined). Temporal trends in duration and interannual variation in migration timing were highly variable across species and populations. The greatest temporal shifts in the median date of migration timing were correlated with decreases in the duration of migration timing, suggestive of a loss of phenotypic variation due to natural selection. Pairwise interannual correlations in migration timing varied widely but were generally positive, providing evidence for weak region‐wide phenological synchrony. This synchrony is likely a function of climatic variation, as interannual variation in migration timing was related to climatic phenomenon operating at large‐ (Pacific decadal oscillation), moderate‐ (sea surface temperature), and local‐scales (precipitation). Surprisingly, the presence or the absence of glaciers within a watershed was unrelated to long‐term shifts in phenology. Overall, there was extensive heterogeneity in long‐term patterns of migration timing throughout this climatically and geographically complex region, highlighting that future climatic change will likely have widely divergent impacts on salmon migration timing. Although salmon phenological diversity will complicate future predictions of migration timing, this variation likely acts as a major contributor to population and ecosystem resiliency in southeast Alaska.

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Molecular adaptations in vasoactive systems during acute stroke in salt-induced hypertension - Nicole M. Ventura; Nichole T. Peterson; M. Yat Tse; R. David Andrew; Stephen C. Pang; Albert Y. Jin (Molecular and Cellular Biochemistry, 2015)

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Effects of enzyme inducers efavirenz and tipranavir/ritonavir on the pharmacokinetics of the HIV integrase inhibitor dolutegravir - Ivy Song; Julie Borland; Shuguang Chen; Phyllis Guta; Yu Lou; David Wilfret; Toshihiro Wajima; Paul Savina; Amanda Peppercorn; Stephen Castellino; David Wagner; Louise Hosking; et al. (European Journal of Clinical Pharmacology, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Reproduction, birth seasonality, and calf survival of bottlenose dolphins in Doubtful Sound, New Zealand - Shaun D. Henderson; Stephen M. Dawson; Rohan J. C. Currey; David Lusseau; Karsten Schneider (Marine Mammal Science, 2014)
Understanding the reproductive parameters of very small or declining populations is of clear importance to conservation. From 1995 to 2011 we recorded calf production ( n = 71) and calf survival for 27 breeding females in the bottlenose dolphin ( Tursiops truncatus ) population in Doubtful Sound, New Zealand; a population with a recent history of declining abundance. Overall, 67% of calves survived their first year, and 40% survived to 3 yr (or are 2 yr old and still alive). Most calves that died in the first year died in their first month (87%). Multiparous mothers ( n = 18) showed high variation in calf survival. The most successful six had all but one of their 20 calves (95%) survive to 1 yr. Fourteen of the 20 (70%) survived to 3 yr, and another four are still alive and are 1 or 2 yr old. In contrast, the least successful seven mothers produced a similar number of calves (21), eight of which (38%) survived to 1 yr, and none to 3 yr. Here we describe calving seasonality and calf survival, observed over 16 yr, and show that large variation in reproductive success of individual females is an example of extreme demographic stochasticity in this small, endangered population.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Gestational hypertension and the developmental origins of cardiac hypertrophy and diastolic dysfunction - David W. J. Armstrong; M. Yat Tse; Philip G. Wong; Nicole M. Ventura; Jalna A. Meens; Amer M. Johri; Murray F. Matangi; Stephen C. Pang (Molecular and Cellular Biochemistry, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Carbon storage in tropical forests correlates with taxonomic diversity and functional dominance on a global scale - Kyle C. Cavanaugh; J. Stephen Gosnell; Samantha L. Davis; Jorge Ahumada; Patrick Boundja; David B. Clark; Badru Mugerwa; Patrick A. Jansen; Timothy G. O'Brien; Francesco Rovero; Douglas Sheil; Rodolfo Vasquez; et al. (Global Ecology and Biogeography, 2014)
Aim We examined (1) the relationships between aboveground tropical forest C storage, biodiversity and environmental drivers and (2) how these relationships inform theory concerning ecosystem function and biodiversity. Experiments have shown that there is a positive relationship between biodiversity and ecosystem functioning, but intense debate exists on the underlying mechanisms. While some argue that mechanisms such as niche complementarity increase ecosystem function, others argue that these relationships are a selection effect. Location Eleven tropical forests in the A mericas, A frica and A sia. Methods We analysed the correlates of biodiversity and carbon storage in tropical forests using data from 59 1‐ha tree plots from a standardized global tropical forest biodiversity‐monitoring network. We examined taxonomic and functional diversity, aboveground C storage and environmental variables in order to determine the relationships between biodiversity and carbon storage in natural (non‐plantation) tropical forests. Results We found that aboveground C storage in tropical forests increased with both taxonomic diversity and functional dominance, specifically the dominance of genera with large maximum diameters, after potential environmental drivers were accounted for (final model R 2 = 0.38, P Main conclusions Our results suggest that niche complementarity and the selection effect are not mutually exclusive: they both play a role in structuring tropical forests. While previous studies have documented relationships between diversity and C storage, these have largely been conducted on small scales in biomes that are relatively species poor compared with tropical forests (e.g. grasslands and temperate or boreal forests). Our results demonstrate that these positive biodiversity–ecosystem functioning relationships are also present in hyperdiverse systems on spatial scales relevant to conservation and management. This insight can be used to inform the conservation and management of tropical forests, which play a critical role in the global carbon cycle and are some of the biologically richest ecosystems on the planet.

Pyrogeography, historical ecology, and the human dimensions of fire regimes - Christopher I. Roos; David M. J. S. Bowman; Jennifer K. Balch; Paulo Artaxo; William J. Bond; Mark Cochrane; Carla M. D'Antonio; Ruth DeFries; Michelle Mack; Fay H. Johnston; Meg A. Krawchuk; Christian A. Kull; et al. (Journal of Biogeography, 2014)
In our 2011 synthesis (Bowman et al ., Journal of Biogeography , 2011, 38 , 2223–2236), we argued for a holistic approach to human issues in fire science that we term ‘pyrogeography’. Coughlan & Petty ( Journal of Biogeography , 2013, 40 , 1010–1012) critiqued our paper on the grounds that our ‘pyric phase’ model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that ‘historical ecology’ could provide such a framework. We used the ‘pyric transition’ for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although ‘historical ecology’ is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

The new sequencer on the block: comparison of Life Technology’s Proton sequencer to an Illumina HiSeq for whole-exome sequencing - Joseph F. Boland; Charles C. Chung; David Roberson; Jason Mitchell; Xijun Zhang; Kate M. Im; Ji He; Stephen J. Chanock; Meredith Yeager; Michael Dean (Human Genetics, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Does increasing the spatial resolution of a regional climate model improve the simulated daily precipitation? - Steven C. Chan; Elizabeth J. Kendon; Hayley J. Fowler; Stephen Blenkinsop; Christopher A. T. Ferro; David B. Stephenson (Climate Dynamics, 2013)

Plant functional types and traits as biodiversity indicators for tropical forests: two biogeographically separated case studies including birds, mammals and termites - Andrew N. Gillison; David E. Bignell; Kenneth R. W. Brewer; Erick C. M. Fernandes; David T. Jones; Douglas Sheil; Peter H. May; Allan D. Watt; Reginaldo Constantino; Eduardo G. Couto; Kurniatun Hairiah; Paul Jepson; et al. (Biodiversity and Conservation, 2013)

A basic residue in the proximal C-terminus is necessary for efficient activation of the M-channel subunit Kv7.2 by PI(4,5)P2 - Vsevolod Telezhkin; Alison M. Thomas; Stephen C. Harmer; Andrew Tinker; David A. Brown (Pflügers Archiv - European Journal of Physiology, 2013)

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Genetic variants associated with VLDL, LDL and HDL particle size differ with race/ethnicity - Alexis C. Frazier-Wood; Ani Manichaikul; Stella Aslibekyan; Ingrid B. Borecki; David C. Goff; Paul N. Hopkins; Chao-Qiang Lai; Jose M. Ordovas; Wendy S. Post; Stephen S. Rich; Michèle M. Sale; David Siscovick; et al. (Human Genetics, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Sex-specific differences in natriuretic peptide and nitric oxide synthase expression in ANP gene-disrupted mice - Philip G. Wong; David W. J. Armstrong; M. Yat Tse; Emily P. A. Brander; Stephen C. Pang (Molecular and Cellular Biochemistry, 2013)

Progressive genome‐wide introgression in agricultural Campylobacter coli - Samuel K. Sheppard; Xavier Didelot; Keith A. Jolley; Aaron E. Darling; Ben Pascoe; Guillaume Meric; David J. Kelly; Alison Cody; Frances M. Colles; Norval J. C. Strachan; Iain D. Ogden; Ken Forbes; et al. (Molecular Ecology, 2013)
Hybridization between distantly related organisms can facilitate rapid adaptation to novel environments, but is potentially constrained by epistatic fitness interactions among cell components. The zoonotic pathogens C ampylobacter coli and C . jejuni differ from each other by around 15% at the nucleotide level, corresponding to an average of nearly 40 amino acids per protein‐coding gene. Using whole genome sequencing, we show that a single C. coli lineage, which has successfully colonized an agricultural niche, has been progressively accumulating C. jejuni DNA . Members of this lineage belong to two groups, the ST ‐828 and ST ‐1150 clonal complexes. The ST ‐1150 complex is less frequently isolated and has undergone a substantially greater amount of introgression leading to replacement of up to 23% of the C. coli core genome as well as import of novel DNA . By contrast, the more commonly isolated ST ‐828 complex bacteria have 10–11% introgressed DNA , and C. jejuni and nonagricultural C. coli lineages each have C. coli that colonize agriculture, and consequently cause most human disease, have hybrid origin, but this cross‐species exchange has so far not had a substantial impact on the gene pools of either C. jejuni or nonagricultural C. coli . These findings also indicate remarkable interchangeability of basic cellular machinery after a prolonged period of independent evolution.

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

“Modeling the impact of natural resource-based poverty traps on food security in Kenya: The Crops, Livestock and Soils in Smallholder Economic Systems (CLASSES) model” - Emma C. Stephens; Charles F. Nicholson; Douglas R. Brown; David Parsons; Christopher B. Barrett; Johannes Lehmann; David Mbugua; Solomon Ngoze; Alice N. Pell; Susan J. Riha (Food Security, 2012)

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Zebrafish: a model for the study of addiction genetics - Eric W. Klee; Henning Schneider; Karl J. Clark; Margot A. Cousin; Jon O. Ebbert; W. Michael Hooten; Victor M. Karpyak; David O. Warner; Stephen C. Ekker (Human Genetics, 2012)

Comparing volunteer and professionally collected monitoring data from the rocky subtidal reefs of Southern California, USA - David J. Gillett; Daniel J. Pondella; Jan Freiwald; Kenneth C. Schiff; Jennifer E. Caselle; Craig Shuman; Stephen B. Weisberg (Environmental Monitoring and Assessment, 2012)

Bacterial community profiles from sediments of the Anacostia River using metabolic and molecular analyses - Karen L. Bushaw-Newton; Evan C. Ewers; David J. Velinsky; Jeffrey T. F. Ashley; Stephen E. MacAvoy (Environmental Science and Pollution Research, 2012)

Genome‐wide analysis of longevity in nutrient‐deprived Saccharomyces cerevisiae reveals importance of recycling in maintaining cell viability - Hazel M. Davey; Emma J. M. Cross; Christopher, L. Davey; Konstantinos Gkargkas; Daniela Delneri; David C. Hoyle; Stephen G. Oliver; Douglas B. Kell; Gareth W. Griffith (Environmental Microbiology, 2012)
Summary Although typically cosseted in the laboratory with constant temperatures and plentiful nutrients, microbes are frequently exposed to much more stressful conditions in their natural environments where survival and competitive fitness depend upon both growth rate when conditions are favourable and on persistence in a viable and recoverable state when they are not. In order to determine the role of genetic heterogeneity in environmental fitness we present a novel approach that combines the power of fluorescence‐activated cell sorting with barcode microarray analysis and apply this to determining the importance of every gene in the Saccharomyces cerevisiae genome in a high‐throughput, genome‐wide fitness screen. We have grown > 6000 heterozygous mutants together and exposed them to a starvation stress before using fluorescence‐activated cell sorting to identify and isolate those individual cells that have not survived the stress applied. Barcode array analysis of the sorted and total populations reveals the importance of cellular recycling mechanisms (autophagy, pexophagy and ribosome breakdown) in maintaining cell viability during starvation and provides compelling evidence for an important role for fatty acid degradation in maintaining viability. In addition, we have developed a semi‐batch fermentor system that is a more realistic model of environmental fitness than either batch or chemostat culture. Barcode array analysis revealed that arginine biosynthesis was important for fitness in semi‐batch culture and modelling of this regime showed that rapid emergence from lag phase led to greatly increased fitness. One hundred and twenty‐five strains with deletions in unclassified proteins were identified as being over‐represented in the sorted fraction, while 27 unclassified proteins caused a haploinsufficient phenotype in semi‐batch culture. These methods thus provide a screen to identifying other genes and pathways that have a role in maintaining cell viability.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Soil-mediated local adaptation alters seedling survival and performance - David Solance Smith; Jennifer A. Schweitzer; Philip Turk; Joseph K. Bailey; Stephen C. Hart; Stephen M. Shuster; Thomas G. Whitham (Plant and Soil, 2012)

Structural changes in the hippocampus and amygdala at first episode of psychosis - David R. Watson; Feng Bai; Suzanne L. Barrett; Aidan Turkington; Teresa M. Rushe; Ciaran C. Mulholland; Stephen J. Cooper (Brain Imaging and Behavior, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Subtle ‘boom and bust’ response of Macquaria ambigua to flooding in an Australian dryland river - David Sternberg; Stephen R. Balcombe; Jonathan C. Marshall; Jaye S. Lobegeiger; Angela H. Arthington (Environmental Biology of Fishes, 2012)

A Critical Re-Examination of the Intraluminal Filament MCAO Model: Impact of External Carotid Artery Transection - Rebecca C. Trueman; David J. Harrison; Dominic M. Dwyer; Stephen B. Dunnett; Mathias Hoehn; Tracy D. Farr (Translational Stroke Research, 2011)

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Gene conversion rapidly generates major histocompatibility complex diversity in recently founded bird populations - LEWIS G. SPURGIN; COCK Van OOSTERHOUT; JUAN CARLOS ILLERA; STEPHEN BRIDGETT; KARIM GHARBI; BRENT C. EMERSON; DAVID S. RICHARDSON (Molecular Ecology, 2011)
Population bottlenecks can restrict variation at functional genes, reducing the ability of populations to adapt to new and changing environments. Understanding how populations generate adaptive genetic variation following bottlenecks is therefore central to evolutionary biology. Genes of the major histocompatibility complex (MHC) are ideal models for studying adaptive genetic variation due to their central role in pathogen recognition. While de novo MHC sequence variation is generated by point mutation, gene conversion can generate new haplotypes by transferring sections of DNA within and across duplicated MHC loci. However, the extent to which gene conversion generates new MHC haplotypes in wild populations is poorly understood. We developed a 454 sequencing protocol to screen MHC class I exon 3 variation across all 13 island populations of Berthelot’s pipit ( Anthus berthelotii ). We reveal that just 11–15 MHC haplotypes were retained when the Berthelot’s pipit dispersed across its island range in the North Atlantic ca. 75 000 years ago. Since then, at least 26 new haplotypes have been generated in situ across populations. We show that most of these haplotypes were generated by gene conversion across divergent lineages, and that the rate of gene conversion exceeded that of point mutation by an order of magnitude. Gene conversion resulted in significantly more changes at nucleotide sites directly involved with pathogen recognition, indicating selection for functional variants. We suggest that the creation of new variants by gene conversion is the predominant mechanism generating MHC variation in genetically depauperate populations, thus allowing them to respond to pathogenic challenges.

Characterisation and predicted genome locations of Leach’s storm-petrel (Oceanodroma leucorhoa) microsatellite loci (Procellariidae, Aves) - Anthony W. J. Bicknell; Deborah A. Dawson; Gavin J. Horsburgh; Mairi E. Knight; David T. Bilton; Stephen C. Votier (Conservation Genetics Resources, 2011)

Screening and confirmatory testing of MHC class I alleles in pig-tailed macaques - Caroline S. Fernandez; Jeanette C. Reece; Uus Saepuloh; Robert De Rose; Diah Ishkandriati; David H. O’Connor; Roger W. Wiseman; Stephen J. Kent (Immunogenetics, 2011)

Host inhibits replication of European porcine reproductive and respiratory syndrome virus in macrophages by altering differential regulation of type-I interferon transcriptional response - Tahar Ait-Ali; Alison D. Wilson; Wilfrid Carré; David G. Westcott; Jean-Pierre Frossard; Marnie A. Mellencamp; Daphne Mouzaki; Oswald Matika; David Waddington; Trevor W. Drew; Stephen C. Bishop; Alan L. Archibald (Immunogenetics, 2011)

Inferring causal factors for a declining population of bottlenose dolphins via temporal symmetry capture–recapture modeling - Rohan J. C. Currey; Stephen M. Dawson; Karsten Schneider; David Lusseau; Oliver J. Boisseau; Patti A. Haase; Elisabeth Slooten (Marine Mammal Science, 2011)
We applied temporal symmetry capture–recapture (TSCR) models to assess the strength of evidence for factors potentially responsible for population decline in bottlenose dolphins ( Tursiops truncatus ) in Doubtful Sound, New Zealand from 1995 to 2008. Model selection was conducted to estimate recruitment and population growth rates. There were similar levels of support for three different models, each reflecting distinct trends in recruitment. Modeling yielded low overall estimates of recruitment (0.0249, 95% CI: 0.0174–0.0324) and population growth rate (0.9642, 95% CI: 0.9546–0.9737). The TSCR rate of population decline was consistent with an estimate derived from trends in abundance (lambda = 0.9632, 95% CI: 0.9599–0.9665). The TSCR model selection confirmed the influence of a decline in the survival of calves (

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

Male reproductive tactics to increase paternity in the polygynandrous Columbian ground squirrel (Urocitellus columbianus) - Shirley Raveh; Dik Heg; Vincent A. Viblanc; David W. Coltman; Jamieson C. Gorrell; F. Stephen Dobson; Adele Balmer; Peter Neuhaus (Behavioral Ecology and Sociobiology, 2011)

Toward a Management Framework for Networks of Protected Areas in the Face of Climate Change - DAVID G. HOLE; BRIAN HUNTLEY; JULIUS ARINAITWE; STUART H. M. BUTCHART; YVONNE C. COLLINGHAM; LINCOLN D. C. FISHPOOL; DEBORAH J. PAIN; STEPHEN G. WILLIS (Conservation Biology, 2011)
Networks of sites of high importance for conservation of biological diversity are a cornerstone of current conservation strategies but are fixed in space and time. As climate change progresses, substantial shifts in species’ ranges may transform the ecological community that can be supported at a given site. Thus, some species in an existing network may not be protected in the future or may be protected only if they can move to sites that in future provide suitable conditions. We developed an approach to determine appropriate climate‐change adaptation strategies for individual sites within a network that was based on projections of future changes in the relative proportions of emigrants (species for which a site becomes climatically unsuitable), colonists (species for which a site becomes climatically suitable), and persistent species (species able to remain within a site despite the climatic change). Our approach also identifies key regions where additions to a network could enhance its future effectiveness. Using the sub‐Saharan African Important Bird Area (IBA) network as a case study, we found that appropriate conservation strategies for individual sites varied widely across sub‐Saharan Africa, and key regions where new sites could help increase network robustness varied in space and time. Although these results highlight the potential difficulties within any planning framework that seeks to address climate‐change adaptation needs, they demonstrate that such planning frameworks are necessary, if current conservation strategies are to be adapted effectively, and feasible, if applied judiciously.

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Wild Turkey (Meleagris gallopavo) association to roads: implications for distance sampling - Devin R. Erxleben; Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Markus J. Peterson; Nova J. Silvy; William P. Kuvlesky; David G. Hewitt; Stephen J. DeMaso; Jason B. Hardin; Megan K. Dominguez-Brazil (European Journal of Wildlife Research, 2011)

Altered expression of the natriuretic peptide system in genetically modified heme oxygenase-1 mice treated with high dietary salt - David W. J. Armstrong; M. Yat Tse; Luis G. Melo; Stephen C. Pang (Molecular and Cellular Biochemistry, 2011)

Expression Analysis of PAC1-R and PACAP Genes in Zebrafish Embryos - David Alexandre; Jessy Alonzeau; Brent R. Bill; Stephen C. Ekker; James A. Waschek (Journal of Molecular Neuroscience, 2011)

Stock structure of Grey Mackerel, Scomberomorus semifasciatus (Pisces: Scombridae) across northern Australia, based on otolith stable isotope chemistry - Stephen J. Newman; Ian W. Wright; Ben M. Rome; Michael C. Mackie; Paul D. Lewis; Rik C. Buckworth; Aaron C. Ballagh; Rod N. Garrett; Jason Stapley; Damien Broderick; Jennifer R. Ovenden; David J. Welch (Environmental Biology of Fishes, 2010)

Population synchrony of a native fish across three Laurentian Great Lakes: evaluating the effects of dispersal and climate - David B. Bunnell; Jean V. Adams; Owen T. Gorman; Charles P. Madenjian; Stephen C. Riley; Edward F. Roseman; Jeffrey S. Schaeffer (Oecologia, 2010)

Body size‐dependent responses of a marine fish assemblage to climate change and fishing over a century‐long scale - MARTIN J. GENNER; DAVID W. SIMS; ALAN J. SOUTHWARD; GEORGINA C. BUDD; PATRICIA MASTERSON; MATTHEW MCHUGH; PETER RENDLE; EMILY J. SOUTHALL; VICTORIA J. WEARMOUTH; STEPHEN J. HAWKINS (Global Change Biology, 2010)
Commercial fishing and climate change have influenced the composition of marine fish assemblages worldwide, but we require a better understanding of their relative influence on long‐term changes in species abundance and body‐size distributions. In this study, we investigated long‐term (1911–2007) variability within a demersal fish assemblage in the western English Channel. The region has been subject to commercial fisheries throughout most of the past century, and has undergone interannual changes in sea temperature of over 2.0 °C. We focussed on a core 30 species that comprised 99% of total individuals sampled in the assemblage. Analyses showed that temporal trends in the abundance of smaller multispecies size classes followed thermal regime changes, but that there were persistent declines in abundance of larger size classes. Consistent with these results, larger‐growing individual species had the greatest declines in body size, and the most constant declines in abundance, while abundance changes of smaller‐growing species were more closely linked to preceding sea temperatures. Together these analyses are suggestive of dichotomous size‐dependent responses of species to long‐term climate change and commercial fishing over a century scale. Small species had rapid responses to the prevailing thermal environment, suggesting their life history traits predisposed populations to respond quickly to changing climates. Larger species declined in abundance and size, reflecting expectations from sustained size‐selective overharvesting. These results demonstrate the importance of considering species traits when developing indicators of human and climatic impacts on marine fauna.

A retrospective evaluation of shortened-duration oral N-acetylcysteine for the treatment of acetaminophen poisoning - David P. Betten; Elizabeth E. Burner; Stephen C. Thomas; Christian Tomaszewski; Richard F. Clark (Journal of Medical Toxicology, 2009)

Boron and Marine Life: A New Look at an Enigmatic Bioelement - Carl J. Carrano; Stephen Schellenberg; Shady A. Amin; David H. Green; Frithjof C. Küpper (Marine Biotechnology, 2009)

Projected impacts of climate change on a continent‐wide protected area network - David G. Hole; Stephen G. Willis; Deborah J. Pain; Lincoln D. Fishpool; Stuart H. M. Butchart; Yvonne C. Collingham; Carsten Rahbek; Brian Huntley (Ecology Letters, 2009)
Despite widespread concern, the continuing effectiveness of networks of protected areas under projected 21st century climate change is uncertain. Shifts in species’ distributions could mean these resources will cease to afford protection to those species for which they were originally established. Using modelled projected shifts in the distributions of sub‐Saharan Africa’s entire breeding avifauna, we show that species turnover across the continent’s Important Bird Area (IBA) network is likely to vary regionally and will be substantial at many sites (> 50% at 42% of IBAs by 2085 for priority species). Persistence of suitable climate space across the network as a whole, however, is notably high, with 88–92% of priority species retaining suitable climate space in ≥ 1 IBA(s) in which they are currently found. Only 7–8 priority species lose climatic representation from the network. Hence, despite the likelihood of significant community disruption, we demonstrate that rigorously defined networks of protected areas can play a key role in mitigating the worst impacts of climate change on biodiversity.

Effects of nutrients and dissolved organic matter on the response of phytoplankton to ultraviolet radiation: experimental comparison in spring versus summer - Caren E. Scott; Jasmine E. Saros; Craig E. Williamson; Courtney R. Salm; Stephen C. Peters; David L. Mitchell (Hydrobiologia, 2009)

Potential health impacts of heavy-metal exposure at the Tar Creek Superfund site, Ottawa County, Oklahoma - John S. Neuberger; Stephen C. Hu; K. David Drake; Rebecca Jim (Environmental Geochemistry and Health, 2009)

Facilitation of extinction of operant behaviour in mice by d-cycloserine - David Shaw; Kelly Norwood; Kim Sharp; Lauren Quigley; Stephen F. J. McGovern; Julian C. Leslie (Psychopharmacology, 2009)

Assessing geochemical carbon management - Jennie C. Stephens; David W. Keith (Climatic Change, 2008)

A Java-based fMRI Processing Pipeline Evaluation System for Assessment of Univariate General Linear Model and Multivariate Canonical Variate Analysis-based Pipelines - Jing Zhang; Lichen Liang; Jon R. Anderson; Lael Gatewood; David A. Rottenberg; Stephen C. Strother (Neuroinformatics, 2008)

Comprehensive evaluation of the estrogen receptor α gene reveals further evidence for association with type 2 diabetes enriched for nephropathy in an African American population - Keith L. Keene; Josyf C. Mychaleckyj; Shelly G. Smith; Tennille S. Leak; Peter S. Perlegas; Carl D. Langefeld; David M. Herrington; Barry I. Freedman; Stephen S. Rich; Donald W. Bowden; Michèle M. Sale (Human Genetics, 2008)

Scaling environmental change through the community‐level: a trait‐based response‐and‐effect framework for plants - KATHARINE N. SUDING; SANDRA LAVOREL; F. S. CHAPIN; JOHANNES H. C. CORNELISSEN; SANDRA DÍAZ; ERIC GARNIER; DEBORAH GOLDBERG; DAVID U. HOOPER; STEPHEN T. JACKSON; MARIE‐LAURE NAVAS (Global Change Biology, 2008)
Predicting ecosystem responses to global change is a major challenge in ecology. A critical step in that challenge is to understand how changing environmental conditions influence processes across levels of ecological organization. While direct scaling from individual to ecosystem dynamics can lead to robust and mechanistic predictions, new approaches are needed to appropriately translate questions through the community level. Species invasion, loss, and turnover all necessitate this scaling through community processes, but predicting how such changes may influence ecosystem function is notoriously difficult. We suggest that community‐level dynamics can be incorporated into scaling predictions using a trait‐based response–effect framework that differentiates the community response to environmental change (predicted by response traits) and the effect of that change on ecosystem processes (predicted by effect traits). We develop a response‐and‐effect functional framework, concentrating on how the relationships among species' response, effect, and abundance can lead to general predictions concerning the magnitude and direction of the influence of environmental change on function. We then detail several key research directions needed to better scale the effects of environmental change through the community level. These include (1) effect and response trait characterization, (2) linkages between response‐and‐effect traits, (3) the importance of species interactions on trait expression, and (4) incorporation of feedbacks across multiple temporal scales. Increasing rates of extinction and invasion that are modifying communities worldwide make such a research agenda imperative.

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

The Biarsenical Dye Lumio™ Exhibits a Reduced Ability to Specifically Detect Tetracysteine-Containing Proteins Within Live Cells - Anna C. Hearps; Melinda J. Pryor; Henna V. Kuusisto; Stephen M. Rawlinson; Sabine C. Piller; David A. Jans (Journal of Fluorescence, 2007)

Are We Consuming Too Much—for What? - HERMAN E. DALY; BRIAN CZECH; DAVID L. TRAUGER; WILLIAM E. REES; MANSI GROVER; TRACY DOBSON; STEPHEN C. TROMBULAK (Conservation Biology, 2007)

Analysis of EST sequences suggests recent origin of allotetraploid colonial and creeping bentgrasses - David Rotter; Arvind K. Bharti; Huaijun Michael Li; Chongyuan Luo; Stacy A. Bonos; Suleiman Bughrara; Geunhwa Jung; Joachim Messing; William A. Meyer; Stephen Rudd; Scott E. Warnke; Faith C. Belanger (Molecular Genetics and Genomics, 2007)

Mechanical shredding of water hyacinth (Eichhornia crassipes): Effects on water quality in the Sacramento-San Joaquin River Delta, California - Ben K. Greenfield; Geoffrey S. Siemering; Joy C. Andrews; Michael Rajan; Stephen P. Andrews; David F. Spencer (Estuaries and Coasts, 2007)

3-Hydroxyglutaric acid is transported via the sodium-dependent dicarboxylate transporter NaDC3 - Franziska Stellmer; Britta Keyser; Birgitta C. Burckhardt; Hermann Koepsell; Thomas Streichert; Markus Glatzel; Sabrina Jabs; Joachim Thiem; Wilhelm Herdering; David M. Koeller; Stephen I. Goodman; Zoltan Lukacs; et al. (Journal of Molecular Medicine, 2007)

An investigation of genome-wide associations of hypertension with microsatellite markers in the family blood pressure program (FBPP) - C. Charles Gu; Steven C. Hunt; Sharon Kardia; Stephen T. Turner; Aravinda Chakravarti; Nicholas Schork; Richard Olshen; David Curb; Cashell Jaquish; Eric Boerwinkle; D. C. Rao (Human Genetics, 2007)

How useful is DNA extracted from the legs of archived insects for microsatellite-based population genetic analyses? - Phillip C. Watts; David J. Thompson; Katherine A. Allen; Stephen J. Kemp (Journal of Insect Conservation, 2007)

Compatible genetic and ecological estimates of dispersal rates in insect ( Coenagrion mercuriale : Odonata: Zygoptera) populations: analysis of ‘neighbourhood size’ using a more precise estimator - PHILLIP C. WATTS; FRANÇOIS ROUSSET; ILIK J. SACCHERI; RAPHAËL LEBLOIS; STEPHEN J. KEMP; DAVID J. THOMPSON (Molecular Ecology, 2007)
Genetic and demographic estimates of dispersal are often thought to be inconsistent. In this study, we use the damselfly Coenagrion mercuriale (Odonata: Zygoptera) as a model to evaluate directly the relationship between estimates of dispersal rate measured during capture–mark–recapture fieldwork with those made from the spatial pattern of genetic markers in linear and two‐dimensional habitats. We estimate the ‘neighbourhood size’ ( Nb ) — the product of the mean axial dispersal rate between parent and offspring and the population density — by a previously described technique, here called the regression method. Because C. mercuriale is less philopatric than species investigated previously by the regression method we evaluate a refined estimator that may be more applicable for relatively mobile species. Results from simulations and empirical data sets reveal that the new estimator performs better under most situations, except when dispersal is very localized relative to population density. Analysis of the C. mercuriale data extends previous results which demonstrated that demographic and genetic estimates of Nb by the regression method are equivalent to within a factor of two at local scales where genetic estimates are less affected by habitat heterogeneity, stochastic processes and/or differential selective regimes. The corollary is that with a little insight into a species’ ecology the pattern of spatial genetic structure provides quantitative information on dispersal rates and/or population densities that has real value for conservation management.

Low Prevalence of BRCA1 Exon Rearrangements in Familial and Young Sporadic Breast Cancer Patients - David Ellis; Yogen Patel; Shu C. Yau; Shirley V. Hodgson; Stephen J. Abbs (Familial Cancer, 2006)

Biocolloid retention in partially saturated soils - Tammo S. Steenhuis; Annette Dathe; Yuniati Zevi; Jennifer L. Smith; Bin Gao; Stephen B. Shaw; Dilkushi DeAlwis; Samary Amaro-Garcia; Rosemarie Fehrman; M. Ekrem Cakmak; Ian C. Toevs; Benjamin M. Liu; et al. (Biologia, 2006)

Tolerance of striped trumpeter Latris lineata embryos to ozonated seawater - Stephen C. Battaglene; David T. Morehead (Aquaculture International, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Diurnal normobaric moderate hypoxia raises serum erythropoietin concentration but does not stimulate accelerated erythrocyte production - Spencer R. McLean; Jon C. Kolb; Stephen R. Norris; David J. Smith (European Journal of Applied Physiology, 2006)

Searching for signals of evolutionary selection in 168 genes related to immune function - Emily C. Walsh; Pardis Sabeti; Holli B. Hutcheson; Ben Fry; Stephen F. Schaffner; Paul I. W. de Bakker; Patrick Varilly; Alejandro A. Palma; Jessica Roy; Richard Cooper; Cheryl Winkler; Yi Zeng; et al. (Human Genetics, 2006)

Estimated Ultraviolet Radiation Doses in Wetlands in Six National Parks - Stephen A. Diamond; Peter C. Trenham; Michael J. Adams; Blake R. Hossack; Roland A. Knapp; Stacey L. Stark; David Bradford; P. Stephen Corn; Ken Czarnowski; Paul D. Brooks; Dan Fagre; Bob Breen; et al. (Ecosystems, 2005)

Science, Policy, and Stakeholders: Developing a Consensus Science Plan for Amchitka Island, Aleutians, Alaska - Joanna Burger; Michael Gochfeld; David Kosson; Charles W. Powers; Barry Friedlander; John Eichelberger; David Barnes; Lawrence K. Duffy; Stephen C. Jewett; Conrad D. Volz (Environmental Management, 2005)

Crown‐stem dimension relationships in two New Zealand native forests - David A. Norton; C. Hamish Cochrane; Stephen D. Reay (New Zealand Journal of Botany, 2005)
The relationships between crown and stem dimensions of trees in two South Island, New Zealand, natural forests were investigated to determine whether they might explain differences in tree species composition estimates based on canopy area and basal area. Dacrydium cupressinum , a common canopy emergent at the lowland podocarp forest site, had the strongest relationship between crown and basal area and a significantly shallower slope than two common understorey trees at that site, Weinmannia racemosa and Quintinia acutifolia. Nothofagus solandri , the only canopy species at the montane beech forest site, showed an intermediate slope and level of correlation. We conclude that differences in estimates of species composition can be at least partly explained by species‐specific differences in the relationship between crown area and basal area and that caution is required in interpreting species relative abundances where different methods have been used to quantify abundance. However, the relationships are not strong enough to warrant the calculation of equations for the prediction of crown area from basal area, as has been done for several open‐grown tree species.

Effect of sampling strategy on measures of V?O2peak obtained using commercial breath-by-breath systems - David W. Hill; Lindsay P. Stephens; Sonja A. Blumoff-Ross; David C. Poole; Jimmy C. Smith (European Journal of Applied Physiology, 2003)

Enhancing anthocyanin production by altering competition for substrate between flavonol synthase and dihydroflavonol 4-reductase - Kevin M. Davies; Kathy E. Schwinn; Simon C. Deroles; David G. Manson; David H. Lewis; Stephen J. Bloor; J. Marie Bradley (Euphytica, 2003)

Functional ecology of shrub seedlings after a natural recruitment event at the Nevada Desert FACE Facility - DAVID C. HOUSMAN; STEPHEN F. ZITZER; TRAVIS E. HUXMAN; STANLEY D. SMITH (Global Change Biology, 2003)
Seedling recruitment is an important determinant of community structure in desert ecosystems. Positive photosynthetic growth and water balance responses to increasing atmospheric carbon dioxide (CO 2 ) concentrations ([CO 2 ]) are predicted to be substantial in desert plants, suggesting that recruitment could be stimulated. However, to date no studies have addressed the response of perennial plant recruitment in natural populations of desert shrubs exposed to elevated [CO 2 ]. In April 1997, we employed Free‐Air Carbon Dioxide Enrichment (FACE) in order to increase atmospheric [CO 2 ] in an undisturbed Mojave Desert ecosystem from ambient (∼∼ 370 µmol mol −1 ) to elevated CO 2 (∼∼ 550 µmol mol −1 ). From 1997 to 2001 we seasonally examined survival, growth, gas exchange and water potential responses of Larrea tridentata and Ambrosia dumosa seedlings that germinated in Fall, 1997. Recruitment densities were not influenced by [CO 2 ] in either species, although a two‐fold higher adult Ambrosia density under elevated [CO 2 ] resulted in two‐fold higher seedling density (0.87 vs 0.40 seedlings m −2 ). Mortality was greatest for both species during the first summer (1998), despite above‐average rainfall during the previous Winter–Spring. A significant [CO 2 ] × time interaction revealed that early survival was greater under elevated CO 2 , whereas a significant species time interaction revealed that overall survival was greater for Ambrosia (28%) than for Larrea ( 15%), regardless of [CO 2 ]. Microsite (understorey or interspace) alone had no significant influence on survival. Significant species, microsite and species × microsite effects on growth (seedling height, stem diameter and canopy size) were found, but elevated CO 2 had minimal impact on these parameters. Photosynthetic rates ( A sat ) for both species were higher at elevated [CO 2 ] during certain seasons, but not consistently so. These results suggest that increased atmospheric [CO 2 ] may enhance carbon (C) assimilation and survival of aridland perennial shrubs during favourable growing conditions, but that it may not counteract the effects of prolonged drought on mortality.

A meta‐analysis of elevated [CO 2 ] effects on soybean ( Glycine max ) physiology, growth and yield - Elizabeth A. Ainsworth; Phillip A. Davey; Carl J. Bernacchi; Orla C. Dermody; Emily A. Heaton; David J. Moore; Patrick B. Morgan; Shawna L. Naidu; Hyung‐shim Yoo Ra; Xin‐guang Zhu; Peter S. Curtis; Stephen P. Long (Global Change Biology, 2002)
The effects of elevated [CO 2 ] on 25 variables describing soybean physiology, growth and yield are reviewed using meta‐analytic techniques. This is the first meta‐analysis to our knowledge performed on a single crop species and summarizes the effects of 111 studies. These primary studies include numerous soybean growth forms, various stress and experimental treatments, and a range of elevated [CO 2 ] levels (from 450 to 1250 p.p.m.), with a mean of 689 p.p.m. across all studies. Stimulation of soybean leaf CO 2 assimilation rate with growth at elevated [CO 2 ] was 39%, despite a 40% decrease in stomatal conductance and a 11% decrease in Rubisco activity. Increased leaf CO 2 uptake combined with an 18% stimulation in leaf area to provide a 59% increase in canopy photosynthetic rate. The increase in total dry weight was lower at 37%, and seed yield still lower at 24%. This shows that even in an agronomic species selected for maximum investment in seed, several plant level feedbacks prevent additional investment in reproduction, such that yield fails to reflect fully the increase in whole plant carbon uptake. Large soil containers (> 9 L) have been considered adequate for assessing plant responses to elevated [CO 2 ]. However, in open‐top chamber experiments, soybeans grown in large pots showed a significant threefold smaller stimulation in yield than soybeans grown in the ground. This suggests that conclusions about plant yield based on pot studies, even when using very large containers, are a poor reflection of performance in the absence of any physical restriction on root growth. This review supports a number of current paradigms of plant responses to elevated [CO 2 ]. Namely, stimulation of photosynthesis is greater in plants that fix N and have additional carbohydrate sinks in nodules. This supports the notion that photosynthetic capacity decreases when plants are N‐limited, but not when plants have adequate N and sink strength. The root : shoot ratio did not change with growth at elevated [CO 2 ], sustaining the charge that biomass allocation is unaffected by growth at elevated [CO 2 ] when plant size and ontogeny are considered.

Comparison of euphausiid population size estimates obtained using replicated acoustic surveys of coastal inlets and block average vs. geostatistical spatial interpolation methods - Stephen J. Romaine; David L. Mackas; Michael C. Macaulay (Fisheries Oceanography, 2002)
Because of their intense patchiness, euphausiid spatial distributions and stock sizes are often assessed using echosounder surveys. However, statistical error bars appropriate for individual survey results are not well known. We quantified these by examining the statistical repeatability of acoustic estimates of total euphausiid biomass within two enclosed fjords adjoining the Strait of Georgia, British Columbia. Within each inlet, paired and replicated `mirror image' zig‐zag survey tracks provided sets of closely spaced backscatter profiles along the survey lines. Local stock density (biomass per unit area) was calculated by vertical integration across the euphausiid scattering layer. Total inlet population size was then estimated by horizontal interpolation and integration of the local measurements, both by block averaging and by geostatistical interpolation (kriging). By assuming no change in true population biomass over the short time interval separating replicate surveys, we could then estimate statistical precision by analysis‐of‐variance comparison among replicate survey grids. For the partial surveys (one or the other half of the mirror‐image paired grid) multiplicative error bars were about a factor of 1.5 for Jervis Inlet and 1.7 for Saanich Inlet. Use of the full surveys (both parts of the mirror‐image pair, roughly doubling the number of measurements in each estimate) reduced the error to about factor of 1.35 for Jervis but only to about 1.65 for Saanich. Statistical precision was similar for the block average vs. kriging interpolation and integration methods, however, kriging provided additional useful information about spatial pattern within the inlets.

Antibiotic resistance in bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) from west Wales - David M. Livermore; Marina Warner; Lucinda M. C. Hall; Virve I. Enne; Stephen J. Projan; Paul M. Dunman; Sarah L. Wooster; Graham Harrison (Environmental Microbiology, 2001)
Summary The prevalence of antibiotic‐resistant bacteria in wild animal and bird populations is largely unknown, with little consistency among the few published reports. We therefore examined intestinal bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) collected in rural west Wales. Escherichia coli isolates resistant to multiple antibiotics were grown from eight of 20 magpies trapped in spring, 1999 and one of 17 in spring, 2000; the most prevalent resistance trait among these isolates was to tetracycline, but resistances to ampicillin, chloramphenicol, kanamycin, sulphonamide, tetracycline and trimethoprim were also found. Tetracycline‐resistant Enterococcus spp. were found in one of 20 magpies in 1999 and three of 17 in 2000. Only one resistant E. coli isolate was detected among gut bacteria from 13 rabbits, and this strain was resistant only to tetracycline. Differences in the prevalence of resistance between bacteria from rabbits and magpies may reflect differences in diet: rabbits graze field edges, whereas magpies are omnivorous and opportunistic. The resistance genes found in E. coli isolates from magpies mostly corresponded to those common among human isolates, but those conferring tetracycline resistance were unique.

Fine mapping of Ath6, a quantitative trait locus for atherosclerosis in mice - Maureen K. Purcell; Jian-Long Mu; David C. Higgins; Ramu Elango; Harry Whitmore; Stephen Harris; Beverly Paigen (Mammalian Genome, 2001)

Visualising active volcanism with high spatial resolution satellite data: the 1991-1993 eruption of Mount Etna - Robert Wright; David A. Rothery; Stephen Blake; David C. Pieri (Bulletin of Volcanology, 2000)

On spatiotemporal patchiness and the coexistence of five species of Chronogaster (Nematoda: Chronogasteridae) in a riparian wetland - Christien H. Ettema; Stephen L. Rathbun; David C. Coleman (Oecologia, 2000)

The Distribution of Nearshore Fishes in Kelp and Eelgrass Communities in Prince William Sound, Alaska: Associations with Vegetation and Physical Habitat Characteristics - Thomas A. Dean; Lewis Haldorson; David R. Laur; Stephen C. Jewett; Arny Blanchard (Environmental Biology of Fishes, 2000)

Improving Forest Inventories: Three Ways to Incorporate Auxiliary Information - Andrew P. Robinson; David C. Hamlin; Stephen E. Fairweather (Journal of Forestry, 1999)
Precise estimates of standing inventory often are needed in a very short time; for example, in appraisal situations for acquisitions and divestitures. Opportunities to integrate auxiliary information into forest stand inventory are considerable, and the potential benefits are very attractive. This article presents three popular techniques for incorporating auxiliary information into forest inventory: list sampling, stratification, and Poisson sampling.

Microbial characterization of a JP‐4 fuel‐contaminated site using a combined lipid biomarker/polymerase chain reaction–denaturing gradient gel electrophoresis (PCR–DGGE)‐based approach - John R. Stephen; Yun‐Juan Chang; Ying Dong Gan; Aaron Peacock; Susan M. Pfiffner; Michael J. Barcelona; David C. White; Sarah J. Macnaughton (Environmental Microbiology, 1999)
The impact of pollution on soil microbial communities and subsequent bioremediation can be measured quantitatively in situ using direct, non‐culture‐ dependent techniques. Such techniques have advantages over culture‐based methods, which often account for less than 1% of the extant microbial community. In 1988, a JP‐4 fuel spill contaminated the glacio‐fluvial aquifer at Wurtsmith Air Force Base, Michigan, USA. In this study, lipid biomarker characterization of the bacterial and eukaryotic communities was combined with polymerase chain reaction– denaturing gradient gel electrophoresis (PCR–DGGE) analysis of the eubacterial community to evaluate correlation between contaminant (JP‐4 fuel) concentration and community structure shifts. Vadose, capillary fringe and saturated zone samples were taken from cores within and up‐ and down‐gradient from the contaminant plume. Lipid biomarker analysis indicated that samples from within the plume contained increased biomass, with large proportions of typically Gram‐negative bacteria. Outside the plume, lipid profiles indicated low‐biomass microbial communities compared with those within the initial spill site. 16S rDNA sequences derived from DGGE profiles from within the initial spill site suggested dominance of the eubacterial community by a limited number of phylogenetically diverse organisms. Used in tandem with pollutant quantification, these molecular techniques should facilitate significant improvements over current assessment procedures for the determination of remediation end‐points.

Strophanthidin-induced gain of Ca 2+ occurs during diastole and not systole in guinea-pig ventricular myocytes - Deborah L. Bennett; Stephen C. O'Neill; David A. Eisner (Pflügers Archiv - European Journal of Physiology, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

The ostracode record from Harris Lake, southwestern Saskatchewan: 9200 years of local environmental change - Stephen C. Porter; David J. Sauchyn; L. Denis Delorme (Journal of Paleolimnology, 1999)

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.

Transferring soils from high‐ to low‐elevation forests increases nitrogen cycling rates: climate change implications - Stephen C. Hart; David A. Perry (Global Change Biology, 1999)
We assessed the potential impact of global warming resulting from a doubling of preindustrial atmospheric CO 2 on soil net N transformations by transferring intact soil cores (0–15 cm) from a high‐elevation old‐growth forest to a forest about 800 m lower in elevation in the central Oregon Cascade Mountains, USA. The lower elevation site had mean annual air and soil (10‐cm mineral soil depth) temperatures about 2.4 and 3.9 °C higher than the high‐elevation site, respectively. Annual rates of soil net N mineralization and nitrification more than doubled in soil transferred to the low‐elevation site (17.2–36.0 kg N ha –1 and 5.0–10.7 kg NO 3 – –N ha –1 , respectively). Leaching of inorganic N from the surface soil (in the absence of plant uptake) also increased. The reciprocal treatment (transferring soil cores from the low‐ to the high‐elevation site) resulted in decreases of about 70, 80, and 65% in annual rates of net N mineralization, nitrification, and inorganic N leaching, respectively. Laboratory incubations of soils under conditions of similar temperature and soil water potential suggest that the quality of soil organic matter is higher at the high‐elevation site. Similar in situ rates of soil net N transformations between the two sites occurred because the lower temperature counteracts the effects of greater substrate quantity and quality at the high elevation site. Our results support the hypothesis that high‐elevation, old‐growth forest soils in the central Cascades have higher C and N storage than their low‐elevation analogues primarily because low temperatures limit net C and N mineralization rates at higher elevations.

The Green University - Stephen C. Trombulak; Susan Bratton; Mark H. Waugh; David Pimentel; James M. Peek (Conservation Biology, 1998)

The Green University - Stephen C. Trombulak; Susan Bratton; Mark H. Waugh; David Pimentel; James M. Peek (Conservation Biology, 1998)

An edited linkage map for the AXB and BXA recombinant inbred mouse strains - Stephen B. Sampson; David C. Higgins; Rosemary W. Elliot; Benjamin A. Taylor; Kira K. Lueders; Robert A. Koza; Beverly Paigen (Mammalian Genome, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Mapping sediment acoustic impedance using remote sensing acoustic techniques in a shallow-water carbonate environment - Donald J. Walter; Douglas N. Lambert; David C. Young; Kevin P. Stephens (Geo-Marine Letters, 1997)

Regulation of desmosomal cell adhesion in human tumour cells by polyunsaturated fatty acids - Wen G. Jiang; Sim K. Singhrao; Stephen Hiscox; Maurice B. Hallett; Richard P. Bryce; David F. Horrobin; Malcolm C. A. Puntis; Robert E. Mansel (Clinical & Experimental Metastasis, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

X-ray absorption spectroscopy of dimethylsulfoxide reductase from Rhodobacter capsulatus - Philippa E. Baugh; C. D. Garner; John M. Charnock; David Collison; E. Stephen Davies; Alan S. McAlpine; S. Bailey; Ian Lane; Graeme R. Hanson; Alastair G. McEwan (JBIC Journal of Biological Inorganic Chemistry, 1997)

Typical Frankia infect actinorhizal plants exotic to New Zealand - Michael L. Clawson; David R. Benson; Steven C. Resch; David W. Stephens; Warwick B. Silvester (New Zealand Journal of Botany, 1997)
Frankia strains are actinomycetes that fix N 2 in root nodules of plants classified in eight families of the Angiospermae. The wide variety of plants infected has raised questions about the ecology and diversity of Frankia symbionts, and their co‐evolution with actinorhizal plants. Partial sequencing was done of the small subunit (16S) rRNA gene from Frankia endophytes present in the root nodules of Alnus cordata , A. glutinosa , A. viridis , Casuarina equisetifolia, Coriaria arborea, C. plumosa , and Elaeagnus pungens growing in New Zealand. With the exceptions of the Coriaria spp., all of the plants are exotic to New Zealand. Analysis of the 16S rRNA gene indicates that the exotic species were nodulated by Frankia strains that cluster with strain groups previously shown to be typical for each actinorhizal host. Frankia in 12 native Coriaria spp. nodules yielded two sequences differing in only one position, suggesting a relatively low diversity compared with the exotic species.

Isolation and Characterization of an Acetylated Impurity in Escherichia coli-Derived Recombinant Human Interleukin-10 (IL-10) Drug Substance - Mollie N. Pflumm; Stephen C. Gruber; Anthony Tsarbopoulos; David Wylie; Birendra Pramanik; James N. Bausch; Suman T. Patel (Pharmaceutical Research, 1997)

Alteration of the quaternary structure of glutamate dehydrogenase from Clostridium symbiosum by a single mutation distant from the subunit interfaces - Jonathan L. E. Dean; H. Cölfen; Stephen E. Harding; David W. Rice; P. C. Engel (European Biophysics Journal, 1997)

Ten Guidelines for Ecosystem Researchers: Lessons from Missouri - David R. Larsen; Stephen R. Shifley; Frank R. Thompson III; Brian L. Brookshire; Daniel C. Dey; Eric W. Kurzejeski; Kristine England (Journal of Forestry, 1997)

Biodiversity within hot spring microbial mat communities: molecular monitoring of enrichment cultures - David M. Ward; Cecilia M. Santegoeds; Stephen C. Nold; Niels B. Ramsing; Michael J. Ferris; Mary M. Bateson (Antonie van Leeuwenhoek, 1997)

The Potato Association of America 75th Annual Meeting Spokane, Washington, U.S.A. - David Curwen; Pete Weingartner; Ronald Knight; Therese M. Work; Hugh J. Murphy; Steven B. Johnson; Richard Zink; Leigh Morrow; A. R. Mosley; Rod Davidson; Thoms Owings; Don Halseth; et al. (American Journal of Potato Research, 1991)

An improved neural-network model for the neural integrator of the oculomotor system: More realistic neuron behavior - Stephen C. Cannon; David A. Robinson (Biological Cybernetics, 1985)

A proposed neural network for the integrator of the oculomotor system - Stephen C. Cannon; David A. Robinson; Shihab Shamma (Biological Cybernetics, 1983)